Mask, method for manufacturing mask, method for manufacturing display device, and display device
The single-piece film formed by laser peeling technology solves the problems of low light transmittance and production efficiency in the prior art, achieves excellent processability and transferability, and improves the light transmittance and production efficiency of mini LED or micro LED displays.
Patent Information
- Application Number
- CN202380066044.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-08-02
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, when manufacturing mini LED or micro LED displays, it is difficult to achieve excellent light transmittance and efficient production processes. Especially when an anisotropic conductive film is pasted directly under the LED, bonding resin and conductive particles remain between the LED spacing, affecting light transmittance and production efficiency.
By using laser peeling technology, a single sheet film having a predetermined shape is formed, including forming a curable resin film on the substrate, and removing unnecessary parts by laser to form a single sheet with excellent processability and transferability. The single-piece film is composed of a curable resin film, and the reaction rate is preferably 25% or less, and is used to connect LED elements and arrange the display device.
The excellent processability and transferability of the single-piece film are achieved, the beat time is improved, the efficient production process is ensured, and the excellent light transmission is achieved in the display.
Smart Images

Figure CN119907728A_ABST
Abstract
Description
Technical Field
[0001] The present technology relates to a method for manufacturing a monolithic film and a monolithic film that monolithically forms connecting films such as anisotropic conductive film (ACF: Anisotropic Conductive Film) and adhesive film (NCF: Non Conductive Film). In addition, the present technology relates to a method for manufacturing a display device and a display device in which light-emitting elements are connected and arranged via a monolithic film. In particular, the present technology relates to a method for manufacturing a display device and a display device in which LED elements such as mini LEDs (Light Emitting Diodes) and micro LEDs are connected and arranged. This application claims priority based on Japanese patent application No. 2022-145312 filed in Japan on September 13, 2022, which is cited in this application by reference. Background Art
[0002] As the next generation of displays, the development of mini LED or micro LED displays has attracted much attention. Mini LED or micro LED displays are composed of tiny light-emitting elements arranged on a substrate, which can omit the backlight required for liquid crystal displays, and can achieve thinner displays, and can also achieve further wide color gamut, high definition, and power saving.
[0003] Patent document 1 discloses a process for bonding LEDs using ACF. In the process described in patent document 1, the ACF is affixed to the component mounting surface of the substrate, so that the adhesive resin and conductive particles of the ACF remain between the LEDs. Therefore, when light transmittance is required for the light-emitting element array, the transmission of light is hindered and excellent light transmittance cannot be obtained. In addition, when the film is set on the entire surface of the substrate, there is a concern that the increase in repair man-hours when a defect occurs will have an adverse effect on production efficiency.
[0004] On the other hand, when the ACF is attached only directly below the LED, the adhesive resin and conductive particles of the ACF do not remain between the LED pitches and do not hinder the transmission of light, thereby achieving light transmittance.
[0005] However, it is difficult to stick a connection film such as ACF only directly below the LED. For example, when a connection film is formed into a single sheet and then stuck to a substrate, if the shape of the single sheet is not good, the transferability of the single sheet to the substrate or LED is deteriorated, and the takt time of display manufacturing is deteriorated. Prior Art Literature Patent Literature
[0006] Patent Document 1: U.S. Patent Application Publication No. 2015 / 0255505 Summary of the invention Problems to be solved by the invention
[0007] The present technology has been proposed in view of such conventional actual conditions, and provides a mask and a method for manufacturing a mask, and a method for manufacturing a display device and a display device that can obtain excellent processability and transferability in a single piece. Solutions to Solve Problems
[0008] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the above-mentioned object can be achieved by the following technology.
[0009] [1] A mask having a light-shielding portion of a predetermined shape in an opening for transmitting laser light, The laser beam is transmitted through the periphery of the light shielding portion. [2] The mask according to [1], wherein the predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle. [3] A method for manufacturing a mask, comprising removing the light-shielding film from a light-transmitting substrate so that a light-shielding portion having a predetermined shape for shielding laser light is provided in an opening for transmitting laser light. [4] A method for manufacturing a display device, comprising: a forming step of irradiating a curable resin film provided on the substrate with a laser from the substrate side, removing the curable resin film in the irradiated portion, and forming a single piece of a predetermined shape composed of a curable resin film having a reaction rate of 25% or less on the substrate; a transfer step of transferring the single piece of the predetermined shape to a predetermined position of a wiring substrate or an electrode surface of a light-emitting element; and The step of mounting the light emitting element on the wiring substrate via the transferred single piece. [5] The method for manufacturing a display device according to [4], wherein in the forming step, the laser light is irradiated through a mask having a light shielding portion having the predetermined shape. [6] The method for manufacturing a display device according to [4], wherein in the transfer step, laser light is irradiated from the substrate side to transfer the single piece of the predetermined shape to a predetermined position of the wiring substrate or an electrode surface of the light-emitting element. [7] According to the method for manufacturing a display device described in [4], the predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oblong, and a circle. [8] According to the method for manufacturing a display device described in [4], the above-mentioned single chip is arranged on the above-mentioned substrate. [9] The method for manufacturing a display device according to [8], wherein the distance between the individual chips is greater than 10 μm.
[10] A display device comprising: a plurality of light emitting elements; A wiring substrate on which the aforementioned light emitting elements are arranged; and a cured film that connects the plurality of light emitting elements to the wiring substrate, The cured film is formed by curing a single piece of a predetermined shape composed of a curable resin film. The predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle.
[11] According to the display device described in
[10] , the distance between the above-mentioned single pieces is greater than 10 μm.
[12] According to the display device described in
[10] , the aforementioned light-emitting elements are arranged in units of sub-pixels that constitute one pixel.
[13] According to the display device described in
[10] , the above-mentioned single chip is arranged in units of sub-pixels or in units of pixels on the above-mentioned wiring substrate. Effects of the Invention
[0010] According to this technology, excellent processability and transferability of a single sheet can be obtained, and the takt time can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a diagram schematically showing an example of the laser lift-off device according to the present embodiment. Figure 2 is a diagram for explaining an example of a method for manufacturing a single-sheet film shown as Specific Example 1, Figure 2 (A) shows a curable resin film substrate in which a curable resin film is formed on a base material, Figure 2 (B) shows the state where the removal portion is peeled off along the first direction, Figure 2 (C) shows the state where the removal portion is peeled off along the second direction. Figure 2 (D) shows a single film in which a curable resin film is formed on a substrate. Figure 3 (A) is a diagram schematically showing an example of a mask in which the opening window portion is a quadrilateral. Figure 3 (B) is a diagram schematically showing an example of irradiating laser light through an opening of a mask. Figure 4 (A) is a microscope photograph showing an example of a single piece in which burrs are generated during processing of the single piece. Figure 4 (B) is a microscope photograph showing an example of a single sheet in which curling or chipping occurs during transfer of the single sheet. Figure 5 (A) is a diagram schematically showing an example of a mask having a light shielding portion in an opening window portion. Figure 5 (B) is a diagram schematically showing an example of irradiating laser light through an opening of a mask. Figure 6 FIG. 1 is a diagram schematically showing an example of a mask having a plurality of light shielding portions in an opening window portion. Figure 7 is a diagram schematically showing an example of the shape of the opening of the mask, Figure 7 (A) shows a mask having a rectangular light shielding portion in an opening window. Figure 7 (B) shows a mask having a square-shaped light shielding portion in the opening window portion. Figure 7 (C) shows a mask having a rectangular light shielding portion with rounded corners in the opening window portion. Figure 7 (D) shows a mask having a circular light shielding portion in an opening window. Figure 8 It is a cross-sectional view schematically showing an anisotropic conductive film provided on a substrate. Fig. 9 It is a cross-sectional view schematically showing a state where the individual film and the wiring substrate are opposed to each other. Fig.10 This is a cross-sectional view schematically showing a state in which laser light is irradiated from the substrate side and individual pieces of anisotropic conductive films are transferred and arranged at predetermined positions on a wiring board. Fig.11 This is a cross-sectional view schematically showing a state in which light emitting elements are mounted on a chip and arranged at predetermined positions on a wiring substrate. Fig.12 This is a cross-sectional view schematically showing a state in which a laser beam is irradiated from the substrate side and a single piece of anisotropic conductive film is transferred and arranged at electrode positions on a wiring substrate. Fig.13 This is a cross-sectional view schematically showing a state in which a light emitting element is mounted on a chip arranged in units of electrodes on a wiring substrate. Fig.14 This is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film provided on a base material and light-emitting elements arranged on a transfer substrate are placed opposite to each other. Fig.15 This is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred onto a light-emitting element arranged on a transfer substrate by irradiating a laser beam from the substrate side. Fig.16 This is a cross-sectional view schematically showing a state in which the light emitting element to which the single chip has been transferred is transferred onto a wiring substrate. Fig.17 It is a figure for demonstrating the positional deviation of a single sheet|seat before and after transfer. Fig.18 is a diagram schematically showing a method for manufacturing a mounting body, Fig.18 (A) shows the process of preparing a single piece, Fig.18 (B) shows the process of transferring the single piece to the substrate, Fig.18 (C) shows the process of temporarily fixing the μLED element. Fig.18 (D) shows the step of press-bonding the μLED element. Fig.19 It is a top view schematically showing an evaluation substrate used for a lighting test. Fig. 20 (A) is a top view schematically showing the electrode surface of a μLED element, Fig. 20 (B) is a diagram schematically showing a state where a μLED element is mounted on an evaluation substrate. Fig.21 It is a top view schematically showing the shape of the mask of Example 1. Fig. 22 It is a top view schematically showing the mask shape of Example 3. Fig.23 It is a top view schematically showing the mask shape of Example 4. Fig.24 It is a top view schematically showing the mask shape of Example 5. Fig.25 This is a microscope photograph showing a single quadrilateral piece of Example 5. Fig.26 It is a top view schematically showing the mask shape of Example 6. Fig. 27 This is a top view schematically showing the mask shape of Example 7. Fig.28 It is a top view schematically showing the mask shape of Example 8. Fig.29 This is a microscope photograph showing a single elliptical piece of Example 8. Fig.30 It is a top view schematically showing the mask shape of Example 9. Fig.31 This is a microscope photograph showing a circular single piece of Example 9. DETAILED DESCRIPTION
[0012] Hereinafter, embodiments of the present technology will be described in detail in the following order while referring to the drawings. 1. Method for manufacturing a monolithic membrane 2. Monolithic membrane 3. Method for manufacturing display device 4. Display device 5. Examples
[0013] <1. Method for manufacturing a single-sheet film> The method for manufacturing a single-piece film according to the present embodiment irradiates a curable resin film provided on a substrate with a laser from the substrate side, removes the irradiated portion of the curable resin film, and forms a single piece of a predetermined shape composed of the curable resin film on the substrate. Here, the reaction rate of the single piece of the predetermined shape is preferably 25% or less, more preferably 20% or less, and further preferably 15% or less. Thus, excellent processability and transferability of the single piece can be obtained.
[0014] In addition, about the measurement of the reaction rate of the curable resin film before laser irradiation or the monolith obtained after laser irradiation, for example, FT-IR can be used to obtain it by the reduction rate of the reactive group. In the case of a small monolith, the reaction rate can also be measured from the end of the film after the monolith is pierced. In addition, it is preferred that the reaction rate of the monolith before laser irradiation is measured within 8 hours after taking it out of a refrigerator and at room temperature, and it is preferred that the reaction rate of the monolith after laser irradiation is measured within 8 hours at room temperature after laser irradiation.
[0015] In the case of a curable resin film utilizing the reaction of an epoxy compound, for example, a sample can be prepared as follows, and the reaction rate can be measured using FT-IR. First, after laser irradiation, a single piece remaining on the substrate is sampled using a sharp-tipped pen-shaped cutter to obtain a sample after laser irradiation. Next, the sampled sample is placed on a diamond unit, becomes thin and flat on the diamond unit, and is mounted on a sample holder and placed in the device body.
[0016] In addition, the diamond unit used in this measurement is a set of two, and the sample is clamped and flattened between two unit plates. After that, a unit plate with a sample is used for measurement. The amount of sample required for measurement is extremely small. If the sample amount is too much, the sample cannot be flattened to be thinner, and the measurement becomes a state in which the sample film thickness is thicker. As a result, the baseline drops or tilts, and the peak is saturated, making it difficult to analyze the spectrum. Therefore, with regard to the sample amount, it is preferred to sample an amount that can be adjusted to a thinner degree on the diamond unit (for example, a degree that can be flattened to a film thickness of less than 10 μm).
[0017] The detector is cooled in advance to greatly improve its sensitivity, so the detector is cooled in advance using liquid nitrogen for about 30 minutes before measurement. In addition, the measurement conditions of FT-IR are set as follows, for example. Measuring method: Transmission Measurement temperature: 25℃ Measuring humidity: below 60% Measuring time: 12 seconds Detector spectral range: 4000 to 700 cm -1
[0018] Furthermore, the diamond unit is placed at an infrared microscope to perform background measurement. By making the background measurement position as close to the sample measurement position as possible, a good baseline can be easily obtained. Next, infrared rays are irradiated to the sample after laser irradiation to obtain the IR spectrum of the curable resin film after laser irradiation. In addition, as with the sample after laser irradiation described above, a pen-shaped cutter with a sharp tip is used to sample the curable resin film before laser irradiation (before singulation) to obtain the IR spectrum of the curable resin film before laser irradiation. Regarding the reaction rate, the methyl group (2930cm -1 Nearby) and epoxy (914cm -1 The peak height of the epoxy group (near the peak height of the methyl group) is calculated as the ratio of the peak height of the epoxy group to the peak height of the methyl group before and after the reaction (for example, before and after laser irradiation) as shown in the following formula. Reaction rate (%) = {1-(a / b) / (A / B)}×100 In the above formula, A is the peak height of the epoxy group before the reaction, B is the peak height of the methyl group before the reaction, a is the peak height of the epoxy group after the reaction, and b is the peak height of the methyl group after the reaction. In addition, when other peaks overlap with the peak of the epoxy group, the peak height of the fully cured sample (reaction rate 100%) can be set to 0%.
[0019] In the case of a curable resin film using a reaction of a (meth)acrylate compound, similarly to epoxy compounds, for example, the methyl group (2930 cm -1 Nearby) and (meth)acryloyl (1635cm -1 The peak height of the (meth)acryloyl group was calculated as the ratio of the peak height of the (meth)acryloyl group to the peak height of the methyl group before and after the reaction.
[0020] In addition, when the peak height of the (meth)acryloyl group is small or has an alicyclic epoxy group or an oxetane group, for example, a sample can be prepared as follows, and the reaction rate can be obtained by HPLC (High Performance Liquid Chromatography). First, after laser irradiation, a pen-shaped cutter with a sharp tip is used to sample the single piece remaining on the substrate to obtain a sample after laser irradiation. Then, after collecting a sample weight of more than 0.015 mg, it is placed in a vial and acetonitrile, an extraction solvent, is added. An arbitrary concentration is determined within the range of 0.025-0.25% to calculate the amount of extraction solvent. Moreover, the vial is placed in the main body of the measuring device, and, for example, under the following measurement conditions, after laser irradiation, HPLC measurement of the single piece remaining on the substrate is performed. In addition, as with the sample after laser irradiation described above, a pen-shaped cutter with a sharp tip is used to sample the curable resin film before laser irradiation (before singulation), and HPLC measurement of the curable resin film before laser irradiation is performed. Extraction: ACN 0.025-0.25% Equipment: UPLC (manufactured by Waters Corporation) Gradient conditions: A60B40 (hold for 1 minute) → A1B99 after 5 minutes (hold for 6 minutes) ※A is water / acetonitrile = 9:1, B is acetonitrile Flow rate: 0.4mL / min Column: 10cm Measurement temperature: 40℃ Injection volume: 5μL
[0021] The reaction rate of a single piece can be calculated from the decay rate of the reactive component before and after the reaction (before and after laser irradiation) according to the chromatogram obtained by HPLC as shown in the following formula. Reaction rate (%) = {1-c / C} × 100 In the above formula, C is the peak height or area of the reactive component before the reaction, and c is the peak height or area of the reactive component after the reaction.
[0022] The substrate can be any substrate that is transmissive to laser light, and quartz glass having a high light transmittance at all wavelengths is particularly preferred. The curable resin film is not particularly limited as long as it is a film that is cured by energy such as heat or light, and can be appropriately selected from, for example, a thermosetting adhesive, a photocurable adhesive, a photothermal curable adhesive, and the like. It is preferred that a reaction initiator is included. In addition, for example, the curable resin film can be formed by using a known method such as mixing / coating / drying.
[0023] [Laser lift-off device] As a device for forming a single piece of a predetermined shape by irradiation with laser, for example, a laser lift-off (LLO: Laser Lift Off) device can be used. The laser lift-off device is a device that irradiates a material layer formed on a substrate with laser light and then peels the material layer off the substrate. Examples of the laser lift-off device include the product "Invisi LUM-XTR" manufactured by Shin-Etsu Chemical Co., Ltd.
[0024] Figure 1 FIG. 1 is a diagram schematically showing an example of a laser lift-off device according to the present embodiment. Figure 1 As shown, the laser lift-off device 10 includes: a laser scanner 11 that scans the optical axis of the laser; a mask 12 that has a plurality of openings of a predetermined shape arranged at a predetermined pitch; a projection lens 13 that reduces and projects the laser onto a donor substrate; a donor stage that holds the donor substrate; and an acceptor stage that holds the acceptor substrate. In forming a single film, a curable resin film substrate 20 having a curable resin film 22 formed on a base material 21 is held on the donor stage as a donor substrate, and the acceptor substrate receives the removed portion 23 of the curable resin film separated from the curable resin film substrate 20.
[0025] As the laser device, for example, an excimer laser that oscillates laser light with a wavelength of 180 nm to 360 nm can be used. The oscillation wavelength of the excimer laser is, for example, 193, 248, 308, or 351 nm, and can be appropriately selected from these oscillation wavelengths in accordance with the light absorptivity of the material of the curable resin film 22. In addition, when an isolation material is provided between the substrate 21 and the curable resin film 22, the isolation material can be appropriately selected in accordance with the light absorptivity of the material.
[0026] The laser scanner 11 has a scanning mirror composed of, for example, a two-axis galvanometer mirror, and scans the optical axis of laser light in the X-axis direction and the Y-axis direction toward the opening in the mask 12 , and controls pulse irradiation of laser light.
[0027] The mask 12 is formed with a pattern of windows arranged at a predetermined pitch and a predetermined size so that the laser irradiation at the interface between the substrate 21 and the curable resin film 22 becomes a predetermined shape. The mask is provided with a pattern, for example, by chrome plating to form a light shielding portion, and the window portion not plated with chrome transmits the laser, while the portion plated with chrome blocks the laser.
[0028] The projection lens 13 projects the laser light having passed through the pattern of the mask 12 onto the donor substrate. The donor stage has a moving mechanism that moves at least in the X-axis and the Y-axis, and moves the irradiation position of the donor substrate with the laser light.
[0029] The laser lift-off device 10 constitutes a scanning type reduction projection optical system including a laser scanner 11, a mask 12, a field lens arranged between the laser scanner 11 and the mask 12, and a reduction projection lens 13 whose image side is telecentric at least.
[0030] The emitted light from the laser device enters the telescopic optical system and propagates to the laser scanner 11 in front of it. The laser light just before entering the laser scanner 11 is adjusted by the telescopic optical system to be substantially parallel light at any position within the moving range of the X-axis and Y-axis of the donor stage, and enters the laser scanner 11 with substantially the same size and the same angle (vertical).
[0031] The laser light from the laser scanner 11 is incident on the mask 12 via the field lens, and the laser light that has passed through the pattern of the mask 12 is incident on the projection lens 13. The laser light emitted from the projection lens 13 is incident from the substrate 21 side, and is accurately projected to a predetermined position of the boundary surface between the substrate 21 and the curable resin film 22 in the shape of the opening of the mask 12. The laser light is projected onto the curable resin film from the opening of the mask, and the curable resin film 22 of the projected portion is removed, leaving the curable resin film of the shape corresponding to the light shielding portion.
[0032] The pulse energy of the laser beam for imaging at the interface between the substrate 21 and the curable resin film 22 is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and even more preferably 0.1 to 1 J. The energy density (fluence) is preferably 0.001 to 2 J / cm 2 , more preferably 0.01 to 1 J / cm 2 , more preferably 0.05 to 0.5 J / cm 2 The pulse width (irradiation time) is preferably 0.01 to 1×10 9 picoseconds, more preferably 0.1 to 1×10 7 picoseconds, more preferably 1 to 1×10 5 The pulse frequency is preferably 0.1 to 10,000 Hz, more preferably 1 to 1,000 Hz, and further preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.
[0033] By using such a laser lift-off device, a shock wave can be generated at the interface between the substrate 21 and the curable resin film 22, so that the removed portion 23 of the curable resin film 22 is peeled off from the substrate 21, and a single piece of a predetermined shape is formed with high precision and efficiency using the remaining portion on the substrate 21, and excellent processability can be obtained. In addition, the influence caused by the irradiation of the laser is small for the single piece of a predetermined shape, so the reaction rate of the single piece can be set to 25% or less, preferably 20% or less, and more preferably 15% or less, and excellent transferability can be obtained. In addition, the measurement of the reaction rate can be obtained by using FT-IR, for example.
[0034] [Specific example 1] In the method for producing a single-piece film shown as Specific Example 1, a mask having a rectangular opening window is used to peel an unnecessary portion of the curable resin film from a substrate, and a rectangular single piece is formed from the remaining portion of the curable resin film.
[0035] Figure 2 is a diagram for explaining an example of a method for manufacturing a single-sheet film shown as Specific Example 1, Figure 2 (A) shows a curable resin film substrate in which a curable resin film is formed on a base material, Figure 2 (B) shows the state where the removal portion is peeled off along the first direction, Figure 2 (C) shows the state where the removal portion is peeled off along the second direction. Figure 2 (D) shows a single film having a curable resin film formed on a substrate. Figure 3 (A) is a diagram schematically showing an example of a mask in which the opening window portion is a quadrilateral. Figure 3 (B) is a diagram schematically showing an example of irradiating laser light through an opening of a mask. Figure 2 and Figure 3 In the embodiment, the number of openings of the mask is set to one, but ideally, a plurality of openings are arranged at a predetermined pitch.
[0036] First, if Figure 2 As shown in (A), a curable resin film substrate 30 having a curable resin film 32 formed on a base material 31 is prepared. Figure 2 (B) and Figure 3 As shown in (B), the curable resin film substrate 30 is turned over, and laser light is irradiated from the substrate 31 side, and the quadrilateral removal portion 33 of the curable resin film 32 is peeled off by the laser light passing through the quadrilateral window portion of the opening of the mask. Figure 3 As shown in (B), the range of the quadrilateral removal portion 33 is moved in the first direction D1 to form a curable resin film having the first direction D1 as the long side direction and the second direction D2 perpendicular to the first direction D1 as the short side direction.
[0037] Next, if Figure 2 (C) and Figure 3 As shown in (B), the range of the quadrilateral removal portion 33 is moved along the second direction D2 with respect to the curable resin film having the first direction D1 as the long side direction and the second direction D2 orthogonal to the first direction D1 as the short side direction. Figure 2 As shown in (D), a square-shaped single piece 34 having a predetermined width in the first direction D1 and a predetermined width in the second direction D2 can be formed.
[0038] When the range of the quadrilateral removal portion 33 is moved in the first direction or the second direction, the range of the quadrilateral removal portion 33 is preferably overlapped. This can suppress the generation of burrs when processing the individual pieces, and suppress curling or chipping when transferring the individual pieces.
[0039] Figure 4 (A) is a microscope photograph showing an example of a single piece in which burrs are generated during processing of the single piece. Figure 4 (B) is a microscopic photograph showing an example of a sheet that has curled or been damaged during transfer. Figure 4 As shown in (A), a single piece 41 with burrs may be formed at the boundary of the range of the adjacent removal portion. The single piece 41 with burrs is difficult to transfer to the correct position, such as Figure 4 As shown in (B), curled individual pieces 42 or chipped individual pieces 43 are formed, and the transfer success rate is reduced.
[0040] [Specific example 2] Regarding the method for manufacturing a single-piece film shown as specific example 2, a mask having a shading portion of a predetermined shape formed in an opening window portion is used to peel off unnecessary portions of the curable resin film around the single piece from a substrate, and a single piece of a predetermined shape is formed by the remaining portions of the curable resin film.
[0041] In specific example 2, the mask (photomask) used in the laser stripping device has a shading portion of a predetermined shape that shields the laser light in the opening that transmits the laser light, and the laser light is transmitted on the periphery of the shading portion. According to such a structure, by irradiating the opening of the mask with laser light, the unnecessary part around the single piece can be peeled off. In addition, as described later, the shape of the shading portion is preferably at least one selected from a polygon composed of obtuse angles, a polygon with rounded corners, an ellipse, an oblong, and a circle. In this way, a single piece with less curling or defects when transferring a single piece using LLO can be obtained.
[0042] Such a mask can be obtained by removing the light-shielding film from a light-transmitting substrate formed with the light-shielding film so that a light-shielding portion of a predetermined shape that shields the laser light is provided in an opening that transmits the laser light. Specifically, the mask can be manufactured by the following steps: an exposure step of preparing a photomask substrate having a light-shielding film of vapor-deposited chromium or the like formed on a quartz glass substrate, uniformly applying a resist (photosensitive resin) to the surface of the photomask substrate, and using an electron beam to draw a pattern of a light-shielding portion of a predetermined shape in the opening; a development step of removing the resist exposed by the electron beam (sometimes also removing the unexposed portion); an etching step of dry etching the exposed portion of the light-shielding film using a reactive gas; and a removal step of removing the remaining resist.
[0043] Figure 5 (A) is a diagram schematically showing an example of a mask having a light shielding portion in an opening window portion. Figure 5 (B) is a diagram schematically showing an example of irradiating laser light through an opening of a mask. Figure 5 (A) and Figure 5 In (B), the number of openings in the mask is one, but it is ideal that a plurality of openings are arranged at a predetermined pitch.
[0044] First, as in Specific Example 1, a curable resin film substrate having a curable resin film formed on a substrate is prepared, the curable resin film substrate is turned over, laser light is irradiated from the substrate side, and the removed portion of the curable resin film is peeled off by the laser light passing through the opening of the mask. Figure 5 As shown in (A), the opening of the mask has a rectangular shading portion 51 at the center of the rectangular window portion, so that the removed portion becomes a donut shape with a rectangular hole at the center of the quadrilateral. The shading portion is preferably scattered in the center of the window portion and is not connected to the window frame. By leaving only the shading portion in the window portion, it is possible to remove the unnecessary portion without moving in the first direction and the second direction as described above. Moreover, as Figure 5 As shown in (B), the range of the quadrilateral removal portion is moved in the first direction and the second direction orthogonal to the first direction, and the same operation is performed, thereby forming quadrilateral individual pieces 52 of the same shape adjacent to each other in the first direction and the second direction.
[0045] According to the method for manufacturing a single-piece film shown as Specific Example 2, the light shielding portion 51 for forming the single piece 52 is provided in the window portion of the opening of the mask, so that the curable resin film around the single piece 52 can be reliably removed. Therefore, the generation of burrs when processing the single piece can be prevented, and curling or damage when transferring the single piece can be suppressed.
[0046] Figure 6 FIG. 1 is a diagram schematically showing an example of a mask having a plurality of light shielding portions in an opening window portion. Figure 5 (A) and Figure 5 In (B), the light shielding portion is set to one in the window of the opening of the mask, but for example Figure 6 As shown, a plurality of light shielding portions 53 may be formed in the window portion of the opening at a predetermined pitch along the X-axis direction and at a predetermined pitch along the Y-axis direction. The size of the window portion (W1×W2) can be determined based on the size of the mask or the maximum value of the effective range of laser irradiation. By using such a mask, a plurality of single pieces can be formed by a single irradiation of the laser.
[0047] [Shape examples of openings] Figure 7 is a diagram schematically showing an example of the shape of the opening of the mask, Figure 7 (A) shows a mask having a rectangular light shielding portion in an opening window. Figure 7 (B) shows a mask having a square-shaped light shielding portion in the opening window portion. Figure 7 (C) shows a mask having a rectangular light shielding portion with rounded corners in the opening window portion. Figure 7 (D) shows a mask having a circular light shielding portion in an opening window.
[0048] The mask openings can also be Figure 7 As shown in (A), a rectangular light shielding portion 54A is provided in the opening window portion, or Figure 7 (B) has a square-shaped light shielding portion 54B, or Figure 7 (C) A rectangular light shielding portion 54C having rounded corners may also be formed. Figure 7 (D) has a circular shading portion 54D. Thus, a rectangular, square, rounded rectangular, or circular single piece can be obtained after the shape of the shading portion is projected. In addition, from the viewpoint of the processability of the single piece and the transfer using LLO, the shape of the shading portion is preferably, for example, a polygon composed of an obtuse angle (an angle greater than 90° and less than 180°), a rounded polygon, an ellipse, an oblong, a circle, or the like. In the case where the shape of the shading portion has an acute angle, the processability of the single piece is deteriorated, and the frequency of curling or defects of the single piece when the single piece is transferred using LLO becomes higher.
[0049] <2. Monolithic film> The monolithic film involved in this embodiment can be obtained by the above-mentioned method for manufacturing a monolithic film. That is, the monolithic film comprises a substrate and a monolithic film of a predetermined shape composed of a curable resin film. Here, the reaction rate of the monolithic film of a predetermined shape is preferably 25% or less, more preferably 20% or less, and further preferably 15% or less. Thus, excellent transferability of the monolithic film can be obtained.
[0050] As mentioned above, in order to suppress curling or defects when transferring a single piece using LLO, the shape of the single piece is preferably at least one selected from a polygon consisting of an obtuse angle, a polygon with rounded corners, an ellipse, an oblong, and a circle. In addition, as mentioned above, the substrate can be any substrate that is transmissive to the laser, and quartz glass having a high light transmittance at all wavelengths is particularly preferred.
[0051] The size (vertical × horizontal) of the monolithic sheet is appropriately set in accordance with the size of the electronic component or the electrode of the electronic component to be connected. The ratio of the area of the monolithic sheet to the area of the electronic component is preferably 0.5 to 5.0, more preferably 0.5 to 4.0, and further preferably 0.5 to 2.0. In addition, the thickness of the monolithic sheet is preferably greater than 1 μm and less than 10 μm, more preferably greater than 1 μm and less than 6 μm, and further preferably greater than 2 μm and less than 4 μm. The thickness of the monolithic sheet can be measured using a known micrometer, digital thickness gauge, laser displacement meter, etc., for example, it can be measured at more than 10 locations and averaged and calculated. The sizes of the monolithic sheets are preferably all the same, but in order to increase the design freedom of the connection structure, there may be multiple types.
[0052] In addition, the distance between the monolithic sheets on the substrate is preferably more than 3 μm, more preferably more than 5 μm, and more preferably more than 10 μm. In addition, the upper limit of the distance between the monolithic sheets is preferably less than 3000 μm, more preferably less than 1000 μm, and more preferably less than 500 μm. When the distance between the monolithic sheets is too small, it is difficult to transfer the monolithic sheets. When the distance between the monolithic sheets is too large, it is preferred to paste the monolithic sheets. The distance between the monolithic sheets can be measured using a microscope (optical microscope, metal microscope, electron microscope, etc.).
[0053] [Curable resin film] As described above, the curable resin film is not particularly limited as long as it is a film that is cured by energy such as heat or light, and can be appropriately selected from, for example, thermosetting adhesives, photocurable adhesives, and photothermal curable adhesives.
[0054] As a thermosetting adhesive, for example, a thermo-anionic polymerization resin composition comprising an epoxy compound and a thermo-anionic polymerization initiator, a thermo-cationic polymerization resin composition comprising an epoxy compound and a thermo-cationic polymerization initiator, a thermo-radical polymerization resin composition comprising a (meth)acrylate compound and a thermo-radical polymerization initiator, etc. can be cited. As a photocurable adhesive, for example, a photo-cationic polymerization resin composition comprising an epoxy compound and a photo-cationic polymerization initiator, a photo-radical polymerization resin composition comprising a (meth)acrylate compound and a photo-radical polymerization initiator, etc. can be cited. As a photothermal curing adhesive, a mixture of a thermosetting adhesive and a photocurable adhesive can be cited. In addition, a (meth)acrylate compound refers to the meaning of any one of an acrylic monomer (oligomer) and a methacrylic monomer (oligomer).
[0055] (Thermal cationic polymerization resin composition) Hereinafter, as a specific example of the thermosetting adhesive, a thermal cationic polymerization type resin composition including a film-forming resin, an epoxy compound, and a thermal cationic polymerization initiator will be described as an example.
[0056] As film-forming resin, for example, it is equivalent to a high molecular weight resin having an average molecular weight of more than 10,000, and from the viewpoint of film formation, it is preferably an average molecular weight of about 10,000 to 80,000. As film-forming resin, various resins such as butyral resin, phenoxy resin, polyester resin, polyurethane resin, polyester polyurethane resin, acrylic resin, polyimide resin can be cited, and they can be used alone or in combination of more than two kinds. From the viewpoints of film formation state, connection reliability, butyral resin is particularly preferably used among them. Relative to 100 parts by mass of thermosetting adhesive, the content of film-forming resin is preferably 20 to 70 parts by mass, more preferably 30 to 60 parts by mass or less, and further preferably 45 to 55 parts by mass.
[0057] The epoxy compound is not particularly limited as long as it has one or more epoxy groups in the molecule, and for example, it may be a bisphenol A epoxy resin, a bisphenol F epoxy resin, or a carbamate-modified epoxy resin. Among them, hydrogenated bisphenol A glycidyl ether can be preferably used. As a specific example of hydrogenated bisphenol A glycidyl ether, for example, the trade name "YX8000" manufactured by Mitsubishi Chemical Corporation can be cited. The content of the epoxy compound is preferably 30 to 60 parts by mass, more preferably 35 to 55 parts by mass or less, and further preferably 35 to 45 parts by mass relative to 100 parts by mass of the thermosetting adhesive.
[0058] As a thermal cationic polymerization initiator, a known material can be used as a thermal cationic polymerization initiator of an epoxy compound, for example, a material that generates an acid that can cause a cationic polymerization compound to undergo cationic polymerization by heat, and known iodonium salts, sulfonium salts, phosphonium salts, ferrocenes, etc. can be used. Among them, aromatic sulfonium salts that show good potential for temperature can be preferably used. As a specific example of an aromatic sulfonium salt polymerization initiator, for example, the trade name "SI-60L" manufactured by Sanshin Chemical Industry Co., Ltd. can be cited. The content of the thermal cationic polymerization initiator is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass or less, and further preferably 8 to 12 parts by mass relative to 100 parts by mass of the thermosetting adhesive.
[0059] In addition, as other additives to be blended into the thermosetting adhesive, rubber components, inorganic fillers, silane coupling agents, diluent monomers, fillers, softeners, colorants, flame retardants, thixotropic agents, etc. may be blended as needed.
[0060] The rubber component is not particularly limited as long as it is an elastomer with high cushioning properties (shock absorption), and specific examples thereof include acrylic rubber, silicone rubber, butadiene rubber, polyurethane resin (polyurethane elastomer), etc. As inorganic fillers, silicon dioxide, talc, titanium oxide, calcium carbonate, magnesium oxide, etc. can be used. As for the inorganic fillers, they can be used alone or in combination of two or more kinds.
[0061] The thermosetting adhesive having such a configuration can suppress the curing reaction when forming the individual pieces by laser light, and can be quickly cured by heat during thermocompression bonding.
[0062] (Anisotropic Conductive Film) In addition, the curable resin film is preferably an anisotropic conductive film further containing conductive particles. As conductive particles, conductive particles used in known anisotropic conductive films can be appropriately selected and used. For example, metal particles such as nickel (melting point 1455°C), copper (melting point 1085°C), silver (melting point 961.8°C), gold (melting point 1064°C), palladium (melting point 1555°C), tin (melting point 231.9°C), nickel boride (melting point 1230°C), ruthenium (melting point 2334°C), and solder as a tin alloy can be listed. In addition, for example, metal-coated metal particles in which the surface of metal particles is coated with metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, and ruthenium can be listed. In addition, for example, metal-coated resin particles that utilize metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, ruthenium to coat the surface of resin particles such as polymers can be cited, and the polymer contains at least one monomer selected from polyamide, polybenzoguanamine, styrene and divinylbenzene as a monomer unit. In addition, for example, metal-coated inorganic particles that utilize metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, ruthenium to coat the surface of inorganic particles such as silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, carbon black, silicate glass, borosilicate glass, lead glass, soda lime glass and alumina silicate glass can be cited. In addition, the coated metal layer of the metal-coated resin particles and the metal-coated inorganic particles can be either a single layer or a multilayer of different types of metals.
[0063] In addition, the insulating coating treatment can also be applied by coating these conductive particles with insulating particles such as resin layers or resin particles, inorganic particles. The particle size of the conductive particles in the present invention does not include the portion of the insulating coating treatment. The particle size of the conductive particles is appropriately changed according to the area of the optical element to be installed, the electrode of the wiring substrate, the bump, etc., but is preferably 1 to 30 μm, more preferably 1 to 10 μm, and particularly preferably 1 to 3 μm. For example, when used in the installation of micro-LED elements, the area of the electrode or the bump is small, so the particle size of the conductive particles is preferably 1 to 3 μm, more preferably 1 to 2.5 μm, and particularly preferably 1 to 2.2 μm. Regarding the particle size, more than 200 can be measured by microscopic observation (optical microscope, metal microscope, electron microscope, etc.) and set as the average value.
[0064] In addition, in the case where the conductive particles are metal-coated resin particles or metal-coated inorganic particles in which the aforementioned resin particles or inorganic particles are coated with metal, the coating thickness of the metal is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.3 μm or less. In the case where the metal coating is multilayer, the coating thickness is the thickness of the entire metal coating. If the coating thickness of the metal is above the above lower limit and below the above upper limit, sufficient conductivity is easily obtained, and in addition, the conductive particles will not become too hard, and it is easy to effectively utilize the characteristics of the aforementioned resin particles or inorganic particles.
[0065] For example, the coating thickness of the metal can be measured by observing the cross section of the conductive particles using a transmission electron microscope (TEM). Regarding the coating thickness, it is preferred to calculate the average value of the coating thicknesses at any five locations as the coating thickness of one conductive particle, and it is more preferred to calculate the average value of the thickness of the entire coating portion as the coating thickness of one conductive particle. It is preferred to calculate the average value of the coating thickness of each conductive particle for any ten conductive particles to obtain the coating thickness.
[0066] In addition, as the shape of the conductive particles, shapes such as spherical, ellipsoidal, spike, and irregular shapes can be listed. Among them, conductive particles with a spherical shape are particularly preferred because it is easy to control the particle size or particle size distribution. In addition, the conductive particles may also have protrusions on the surface in order to improve connectivity.
[0067] Anisotropic conductive film is preferably formed by arranging conductive particles in the surface direction. By arranging conductive particles in the surface direction, the particle surface density becomes uniform, and conductivity and insulation can be improved. The so-called state of conductive particles arranged in the surface direction, for example, a plane lattice pattern with more than one arrangement axis of conductive particles arranged in a predetermined direction at a predetermined interval can be listed, and rhombic lattices, hexagonal lattices, square lattices, rectangular lattices, parallelograms, etc. can be listed. In addition, the arrangement of the surface direction of conductive particles can be random or have multiple regions with different plane lattice patterns.
[0068] The particle surface density of the anisotropic conductive film can be appropriately designed according to the size of the electrode to be connected, and the lower limit of the particle surface density can be set to 500 particles / mm 2 Above, 20000 pieces / mm 2 Above, 40000 pieces / mm 2 Above, 50000 pieces / mm 2 The upper limit of the particle surface density can be set to 1500000 particles / mm 2 Below, 1,000,000 pieces / mm 2 Below, 500,000 pieces / mm2 Below, 100,000 pieces / mm 2 As a result, even when the electrode size of the connection object is small, excellent conductivity and insulation can be obtained. The particle surface density of the anisotropic conductive film is the particle surface density of the arrangement part of the conductive particles when the film is formed during manufacturing. In the case of obtaining the particle number density based on multiple monoliths, the particle surface density can be obtained based on the area after removing the interval between the monoliths from the area including the monoliths and the intervals and the number of particles.
[0069] The anisotropic conductive film is easy to be provided on the substrate by being provided in a film shape. From the viewpoint of operability, a release film such as a polyethylene terephthalate film may be provided on one or both sides of the anisotropic conductive film. In addition, the anisotropic conductive film may be laminated with an adhesive layer or a pressure-sensitive adhesive layer that does not contain conductive particles, and the number of layers or the laminated surface may be appropriately selected in accordance with the object or purpose.
[0070] The thickness of the anisotropic conductive film can be appropriately changed according to the height of the electrode or bump of the optical element or wiring substrate to be installed, as long as it is within 1 to 10 times the particle size, preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 6 μm or less, and further preferably 2 μm or more and 4 μm or less. The film thickness can be measured using a known micrometer or digital thickness gauge. For example, more than 10 locations can be measured and the film thickness can be averaged to obtain the film thickness.
[0071] Examples of a method for producing an anisotropic conductive film include a method of applying a solution of an anisotropic conductive adhesive on a substrate and drying the solution, and a method of forming an adhesive layer containing no conductive particles on a substrate and fixing conductive particles to the resulting adhesive layer.
[0072] <3. Method for manufacturing display device> The manufacturing method of the display device according to the present embodiment comprises: a forming step of irradiating a curable resin film provided on a substrate with a laser from the substrate side, removing the irradiated portion of the curable resin film, and forming a single piece of a predetermined shape composed of the curable resin film on the substrate; a transfer step of transferring the single piece of a predetermined shape to a predetermined position of a wiring substrate or an electrode surface of a light-emitting element; and a mounting step of mounting the light-emitting element on the wiring substrate via the transferred single piece. Thus, the excellent processability and transferability of the single piece can be obtained, and the takt time can be shortened.
[0073] The shape of the single piece is formed corresponding to the shape of the wiring substrate and the electrode of the light emitting element. As mentioned above, in order to improve the processability of the single piece and suppress the curling or defect when transferring the single piece using LLO, it is preferably at least one selected from a polygon composed of obtuse angles, a polygon with rounded corners, an ellipse, an oblong circle, and a circle. In addition, the curable resin film may also be an anisotropic conductive film.
[0074] A single chip can be arranged in units of one pixel (for example, one pixel of one group of RGB), that is, in units of multiple light-emitting elements, or in units of sub-pixels constituting one pixel (for example, any number of RGB), that is, in units of light-emitting elements. Thus, it can correspond to a light-emitting element array with a high PPI (Pixels Per Inch) to a light-emitting element array with a low PPI. In addition, for example, when RGB is set as one pixel, three sub-pixels are set as one group or a total of six sub-pixels including three sub-pixels of a redundant circuit of RGB are set as one group and arranged, so a single chip can also be arranged in units of one group of six sub-pixels.
[0075] Alternatively, the individual chips may be arranged in units of electrodes corresponding to the first conductive type electrode on the p side or the second conductive type electrode on the n side of the light emitting element. Alternatively, the individual chips may be arranged in units of a range that does not impair transparency (e.g., 1 mm×1 mm) in order to improve production efficiency.
[0076] In addition, in the formation process, in order to efficiently remove the unnecessary part of the curable resin film, the curable resin film can also be pretreated. As pretreatment, for example, a monolithic cut of the light-emitting element unit or the electrode unit, a grid-like cut in which a plurality of cuts in the longitudinal direction and a plurality of cuts in the transverse direction intersect, etc. can be listed. The cut can be set using a mechanical method, a chemical method, a laser, etc. In addition, the cut can be not deep enough to reach the substrate, or it can be half-cut. Thus, curling of the monolithic film can be suppressed.
[0077] In addition, the transfer method of the single chip in the transfer process is not particularly limited, but for example, a method of directly transferring the single chip from the substrate and arranging it on the wiring substrate or the light-emitting element by the aforementioned laser lift-off method (LLO method) or a method of transferring from the transfer material and arranging it on the wiring substrate or the light-emitting element using a transfer material (mold material) to which the single chip is pre-adhered.
[0078] In addition, the method for configuring the light-emitting element in the installation process is not particularly limited, but for example, a method of configuring the light-emitting element on the wiring substrate by the aforementioned laser lift-off method (LLO method) or a method of configuring the light-emitting element from the transfer material to the wiring substrate using a transfer material (mold material) to which the light-emitting element is pre-adhered can be listed.
[0079] [First embodiment] The manufacturing method of the display device involved in the first embodiment includes: a forming step (A1), which uses a laser peeling device to remove the anisotropic conductive film in the laser irradiated portion, and forms a single piece of a predetermined shape composed of the anisotropic conductive film on the substrate; a transfer step (B1), which uses a laser peeling device to transfer the single piece of a predetermined shape to a predetermined position on the wiring substrate; and a mounting step (C1), which uses a laser peeling device to arrange the light-emitting element at a predetermined position on the wiring substrate, so that the light-emitting element is mounted on the wiring substrate.
[0080] Below, refer to Figures 8 to 11 The following describes a step (A1) of forming a single piece of a predetermined shape, a transfer step (B1) of transferring the single piece of the predetermined shape, and a mounting step (C1) of mounting a light emitting element on a wiring board.
[0081] [Formation step (A1)] In the forming step (A1), an anisotropic conductive film is prepared on a substrate, and the laser is irradiated from the substrate side using the aforementioned laser lift-off device, and the removed portion of the anisotropic conductive film is lifted off by the laser through the opening of the aforementioned mask to form a single sheet. The method for forming a single sheet is the same as the method for manufacturing the aforementioned single sheet film, and therefore a detailed description is omitted here.
[0082] Figure 8 Schematically shows a cross-sectional view of an anisotropic conductive film provided on a substrate. Here, it is preferred that a region X exists along the thickness direction from the substrate 61 side of the anisotropic conductive film 62, and no conductive particles exist in the region X. The state in which no conductive particles exist in the region X, for example, means not only a state in which the entire particles of the conductive particles 63 do not exist in the region, but also a state in which no part of the conductive particles 63 is included. In other words, it is preferred that all the conductive particles 63 exist in the portion of the anisotropic conductive film 62 other than the region X without exceeding.
[0083] In addition, from the perspective of production efficiency of the anisotropic conductive film 62, the region X existing in the thickness direction from the substrate 61 side of the anisotropic conductive film 62 is preferably set to be less than 5% of the number of the entire conductive particles 63 contained in the anisotropic conductive film 62, and more preferably set to be less than 1%.
[0084] The thickness t of the region X of the anisotropic conductive film 62 from the substrate 61 side can be 0 to 0.05 μm. In order to more reliably suppress the degradation of the conductive particles 63 caused by ablation, it is preferably 0 to 0.1 μm, more preferably 0 to 0.15 μm, and particularly preferably 0 to 0.2 μm. The region X may also be greater than 0.2 μm. In addition, the lower limit is only required to be greater than 0, which means that up to 5% of the number of the total conductive particles 63, preferably up to 1%, do not reach (do not touch) the substrate 61. The cross section can be confirmed by observation with an electron microscope.
[0085] In addition, from the viewpoint of improving ablation resistance, the conductive particles 63 preferably contain a metal having a melting point of 1400° C. or higher. From the viewpoint of easy availability, the upper limit of the melting point of the metal is preferably about 3500° C. In addition, from the viewpoint of easy availability, the metal constituting the conductive particles 63 preferably contains nickel, palladium, or ruthenium.
[0086] In addition, when using metal-coated resin particles in which the surfaces of the aforementioned resin particles are coated with metal or metal-coated inorganic particles in which the surfaces of inorganic particles are coated with metal as the conductive particles 63, in order to minimize the influence of ablation on the resin particles or inorganic particles, the coating thickness of the metal is preferably set to 0.04 μm or more, more preferably to 0.5 μm or more, particularly preferably to 0.75 μm or more, and most preferably to 0.1 μm or more. The upper limit of the coating thickness of the metal depends on the diameter of the conductive particles 63, but is preferably 20% of the diameter of the conductive particles 63 or about 0.5 μm.
[0087] [Transfer process (B)] Fig. 9 2 is a cross-sectional view schematically showing a state where a single film and a wiring substrate are placed opposite to each other. Fig. 9 As shown, first, in the transfer step (A), the individual film 60 and the wiring substrate 70 are placed opposite to each other.
[0088] The monolithic film 60 includes a substrate 61 and a monolithic film 64 composed of an anisotropic conductive film containing conductive particles 63, and the monolithic film 64 is arranged on the surface of the substrate 61 in units of light-emitting elements. The substrate 61 can be any substrate that is transmissive to laser light, and quartz glass having high light transmittance at all wavelengths is particularly preferred.
[0089] The size (vertical × horizontal) of the single chip 64 is appropriately set in accordance with the size of the light-emitting element as a chip component, and the ratio of the area of the single chip 64 to the area of the light-emitting element is preferably 0.5 to 5.0, more preferably 0.5 to 4.0, and further preferably 0.5 to 2.0. In addition, the thickness of the single chip 64 is preferably 2 to 10 μm, more preferably 3 to 8 μm or less, and further preferably 4 to 6 μm or less. The sizes of the single chips are preferably all the same, but in order to increase the design freedom of the connection structure, there may be multiple types. Thus, a connection structure having excellent light transmittance, conductivity and insulation that cannot be achieved in the connection of the previous ACP (Anisotropic Conductive Paste), ACF (Anisotropic Conductive Film), NCF (Non Conductive Film), adhesives, etc. can be obtained.
[0090] In addition, the distance between the single pieces arranged on the substrate 61 is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. In addition, the upper limit of the distance between the single pieces is preferably 3000 μm or less, more preferably 1000 μm or less, and further preferably 500 μm or less. When the distance between the single pieces is too small, it is difficult to transfer the single piece. When the distance between the single pieces is too large, the method of pasting the single piece is preferred. The distance between the single pieces can be measured using a microscope (optical microscope, metal microscope, electron microscope, etc.).
[0091] The wiring substrate 70 has a circuit pattern for the first conductive type and a circuit pattern for the second conductive type on a substrate 71, for example, a first electrode 72 and a second electrode 73 are respectively provided at positions corresponding to the first conductive type electrode on the p-side and the second conductive type electrode on the n-side, so that the light-emitting elements are arranged in units of sub-pixels (sub-pixels) constituting one pixel. In addition, the wiring substrate 70 forms a circuit pattern such as a data line and an address line of a matrix wiring, and can connect and disconnect the light-emitting elements corresponding to each sub-pixel constituting one pixel. For example, one pixel can also be composed of three sub-pixels of R (red), G (green), and B (blue), or four sub-pixels of RGBW (white) and RGBY (yellow), or two sub-pixels of RG and GB.
[0092] In addition, when the wiring substrate 70 is used for transparent display applications, it is preferably a light-transmitting substrate, and the base material 71 is preferably glass, PET (Polyethylene Terephthalate), etc. The first electrode 72 and the second electrode 73 are preferably transparent conductive films such as ITO (Indium-Tin-Oxide), IZO (Indium-Zinc-Oxide), ZnO (Zinc-Oxide), and IGZO (Indium-Gallium-Zinc-Oxide).
[0093] Fig.10 2 is a cross-sectional view schematically showing a state in which a laser is irradiated from the substrate side and a single piece of anisotropic conductive film is transferred and arranged at a predetermined position on a wiring substrate. Fig.10 As shown, in the transfer step (B), the laser lift-off device described above is used to irradiate laser light from the substrate 61 side, and the single piece 64 of the anisotropic conductive film is transferred and arranged at a predetermined position on the wiring substrate 70. By aligning the substrate 61 and the substrate 70 and transferring, the single piece 64 can be arranged on the substrate 70 in units of sub-pixels.
[0094] When the size of the substrate 70 is larger than that of the base material 61 , the base material 61 is aligned multiple times and the individual pieces 64 are transferred, so that the individual pieces 64 can be arranged in units of sub-pixels in the screen area of the substrate 70 .
[0095] In the transfer of the single piece 64 of the anisotropic conductive film, the aforementioned laser lift-off device can be used. Such a transfer method is called laser lift-off, and is, for example, a method using ablation by laser. In the aforementioned laser lift-off device, the single piece of film 60 as a donor substrate is held on a donor stage, and the wiring substrate 70 as an acceptor substrate is held on an acceptor stage. The distance between the single piece of film and the wiring substrate is preferably 10 to 20,000 μm, more preferably 50 to 1,500 μm, and further preferably 80 to 1,000 μm.
[0096] As the laser device, for example, an excimer laser oscillating a laser beam with a wavelength of 180 nm to 360 nm can be used. The oscillation wavelength of the excimer laser is, for example, 193, 248, 308, or 351 nm, and can be appropriately selected from these oscillation wavelengths according to the light absorption of the material of the anisotropic conductive film.
[0097] The mask uses a pattern in which windows of a predetermined pitch and a predetermined size are arranged so that the projection at the interface between the substrate 61 and the single piece 64 of the anisotropic conductive film becomes a desired arrangement of laser light. The pattern is applied to the substrate 61 by, for example, chrome plating, and the window portions not plated with chrome transmit the laser light, while the portions plated with chrome block the laser light.
[0098] The emitted light from the laser device enters the telescopic optical system and propagates to the laser scanner 11 in front of it. The laser light just before entering the laser scanner 11 is adjusted by the telescopic optical system to be substantially parallel light at any position within the moving range of the X-axis and Y-axis of the donor stage, and enters the laser scanner 11 with substantially the same size and the same angle (vertical).
[0099] The laser light from the laser scanner 11 is incident on the mask 12 via the field lens, and the laser light that has passed through the pattern of the mask 12 is incident on the projection lens 13. The laser light emitted from the projection lens 13 is incident from the substrate 61 side, and is accurately projected at the position of the single piece 64 of the anisotropic conductive film formed on the surface (lower surface) thereof at a reduced size of the mask pattern.
[0100] The pulse energy of the laser beam for imaging the interface between the single piece of the anisotropic conductive film and the substrate is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and further preferably 0.1 to 1 J. The energy density (fluence) is preferably 0.001 to 2 J / cm 2 , more preferably 0.01 to 1 J / cm 2 , more preferably 0.05 to 0.5 J / cm 2 The pulse width (irradiation time) is preferably 0.01 to 1×10 9 picoseconds, more preferably 0.1 to 1×10 7 picoseconds, more preferably 1 to 1×10 5 The pulse frequency is preferably 0.1 to 10,000 Hz, more preferably 1 to 1,000 Hz, and further preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.
[0101] By using such a laser lift-off device, a shock wave is generated on the laser-irradiated single piece 64 at the interface between the substrate 61 and the single piece 64 of the anisotropic conductive film, and the single piece 64 is peeled off from the substrate 61 and lifted toward the wiring substrate 70, so that a plurality of single pieces 64 can be landed at predetermined positions on the wiring substrate 70. Thus, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the wiring substrate 70 with high precision and high efficiency, and the cycle time can be shortened.
[0102] The reaction rate of the single piece 64 of the anisotropic conductive film after the transfer step (B1) is preferably 25% or less, more preferably 20% or less, and further preferably 15% or less. The reaction rate of the single piece 64 after the transfer step (B1) is 25% or less, so that the light-emitting element can be thermally pressed in the mounting step (C1). The reaction rate can be measured, for example, using FT-IR.
[0103] In addition, the distance between the single pieces arranged at the predetermined position of the wiring substrate 70 is the same as the distance between the single pieces arranged on the substrate 61 of the single piece film 60, preferably 3 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. In addition, the upper limit of the distance between the single pieces is preferably 3000 μm or less, more preferably 1000 μm or less, and further preferably 500 μm or less. In the case where the distance between the single pieces is too small, it is preferred to paste the anisotropic conductive film on the entire surface of the wiring substrate 70. In the case where the distance between the single pieces is too large, it is preferred to paste the anisotropic conductive film on the predetermined position of the wiring substrate 70. The distance between the single pieces can be measured by microscopic observation (optical microscope, metal microscope, electron microscope, etc.).
[0104] [Installation process (C1)] Fig.11 FIG. 1 is a cross-sectional view schematically showing a state in which light emitting elements are mounted on a single chip arranged at a predetermined position on a wiring substrate. Fig.11 As shown, in the mounting step ( C1 ), the light emitting element 80 is mounted on the chip 64 arranged at a predetermined position on the wiring substrate 70 .
[0105] The light emitting element 80 includes a main body 81, a first conductive type electrode 82, and a second conductive type electrode 83, and has a horizontal structure in which the first conductive type electrode 82 and the second conductive type electrode 83 are arranged on the same surface. The main body 81 includes a first conductive type cladding layer composed of, for example, n-GaN, a first conductive type cladding layer composed of, for example, In x Al y Ga 1-x-y The active layer composed of an N layer and the second conductive type cladding layer composed of, for example, p-GaN have a so-called double heterostructure. The first conductive type electrode 82 is formed on a part of the first conductive type cladding layer through a passivation layer, and the second conductive type electrode 83 is formed on a part of the second conductive type cladding layer. If a voltage is applied between the first conductive type electrode 82 and the second conductive type electrode 83, carriers are concentrated in the active layer and light is generated by recombination.
[0106] The light emitting elements 80 are arranged on the substrate 70 corresponding to the sub-pixels constituting one pixel, forming a light emitting element array. For example, one pixel may be composed of three sub-pixels of R (red), G (green), and B (blue), or four sub-pixels of RGBW (white) and RGBY (yellow), or two sub-pixels of RG and GB.
[0107] As the arrangement method of sub-pixels, for example, in the case of RGB, stripe arrangement, mosaic arrangement, triangle arrangement, etc. can be cited. Stripe arrangement arranges RGB in a vertical stripe shape, which can achieve high precision. In addition, mosaic arrangement arranges the same color of RGB obliquely, which can obtain a more natural image than stripe arrangement. In addition, triangle arrangement arranges RGB in a triangle, and each point is offset by half a pitch in each field, which can obtain a natural image display.
[0108] In the mounting step (C1), the aforementioned laser lift-off device can be used to arrange the light emitting element 80 at a predetermined position of the wiring substrate 70. In the aforementioned laser lift-off device, the light emitting element as a donor substrate is held on a donor stage, and the wiring substrate 70 as an acceptor substrate is held on an acceptor stage. The distance between the light emitting element and the wiring substrate is preferably 10 to 1000 μm, more preferably 50 to 500 μm, and further preferably 80 to 200 μm.
[0109] As a method for connecting the light-emitting element 80 to the wiring substrate 70, a connection method such as thermocompression bonding, optical compression bonding, and thermo-optical compression bonding used in the known anisotropic conductive film can be appropriately selected and used. In addition, when the conductive particles are solder particles, the connection can also be made by reflow soldering. As conditions for thermocompression bonding, for example, a temperature of 150°C to 260°C, a pressure of 1MPa to 60MPa, and a time of 5 seconds to 300 seconds. The anisotropic conductive film is cured to form a cured film, and in a state where there is no cured film between the light-emitting elements 80 and the wiring substrate 70 is exposed, the light-emitting element 80 can be anisotropically connected to the wiring substrate 70. In addition, by setting the wiring substrate 70 as a light-transmitting substrate, compared with the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate 70, excellent light transmittance can be obtained.
[0110] [Modification of the first embodiment] In the transfer step (B1) of the first embodiment described above, Fig. 9 and Fig.10 As shown, the single piece 64 of the anisotropic conductive film is arranged on the wiring substrate 70 in units of sub-pixels as light-emitting element units, but is not limited to this. For example, it can also be arranged in units of electrodes corresponding to the first conductive type electrode on the p side or the second conductive type electrode on the n side of the light-emitting element.
[0111] Fig.12 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred and arranged at electrode positions on a wiring substrate by irradiating laser light from the substrate side. Fig.13 FIG. 1 is a cross-sectional view schematically showing a state in which a light emitting element is mounted on a single chip arranged in units of electrodes on a wiring substrate. Fig.12 As shown, in the transfer step (B1), the first single piece 64A and the second single piece 64B are transferred to the first electrode 72 and the second electrode 73 corresponding to the first conductive electrode 82 on the p side and the second conductive electrode 83 on the n side of the light emitting element 80, respectively.
[0112] The size (vertical x horizontal) of the single pieces 64A and 64B is appropriately set according to the size of the electrode of the light-emitting element. As in the case where the single piece is formed per light-emitting element, the ratio of the area of the single piece to the area of the electrode is preferably 0.5 to 5.0, more preferably 0.5 to 4.0, and even more preferably 0.5 to 2.0. In addition, the thickness of the single piece is preferably 2 to 10 μm, more preferably 3 to 8 μm or less, and even more preferably 4 to 6 μm or less.
[0113] like Fig.13 As shown, in the mounting step (C1), the light emitting element 80 is mounted on the individual pieces 64A and 64B arranged in units of electrodes on the wiring substrate 70. This can further improve the transparency of the display device.
[0114] As described above, according to the manufacturing method of the display device involved in the first embodiment, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the wiring substrate 70 with high accuracy and high efficiency by irradiation with laser, so that the takt time can be shortened. In addition, excellent light transmittance, conductivity and insulation that cannot be achieved by the connection of the conventional ACP, ACF, NCF, adhesive, etc. can be obtained, and a high-brightness and high-definition transparent display can be obtained.
[0115] [Second embodiment] The manufacturing method of the display device according to the second embodiment includes: a forming step (A2) of removing the anisotropic conductive film of the laser irradiated portion using a laser lift-off device to form a single piece of a predetermined shape composed of the anisotropic conductive film on a substrate; a transfer step (B2-1) of transferring the single piece of a predetermined shape to the electrode surface of the light-emitting element using a laser lift-off device; a re-transfer step (B2-2) of re-transferring the light-emitting element to which the single piece has been transferred to a predetermined position on a wiring substrate using a laser lift-off device; and a mounting step (C2) of mounting the light-emitting element on the wiring substrate. Thus, the excellent processability and transferability of the single piece can be obtained, and the takt time can be shortened.
[0116] Below, refer to Figures 14 to 16 The following describes a step (A2) of forming a single chip of a predetermined shape, a transfer step (B2-1) of transferring the single chip of a predetermined shape to the electrode surface of a light-emitting element, a re-transfer step (B2-2) of re-transferring the light-emitting element to which the single chip has been transferred to a predetermined position on a wiring substrate, and a mounting step (C2) of mounting the light-emitting element on the wiring substrate. In addition, the same reference numerals are given to the same components as those in the first embodiment, and the description thereof is omitted.
[0117] [Formation step (A2)] The forming step (A2) is the same as the forming step (A1) in the first embodiment, and thus detailed description thereof is omitted here.
[0118] [Transfer process (B2-1)] Fig.14 2 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film provided on a substrate and light-emitting elements arranged on a transfer substrate are placed opposite to each other. Fig.14 As shown, in the transfer step (B2), the single piece 64 of the anisotropic conductive film provided on the base material 61 is placed opposite to the transfer substrate 90. The single piece 64 is formed on the base material 61 in a shape corresponding to the electrode of the light emitting element 50.
[0119] The transfer substrate 90 includes a substrate 91 and light emitting elements 80 arranged on the substrate 91. The substrate 91 is appropriately selected according to the transfer method of the re-transfer step (B2-2) described later. For example, in the re-transfer step (B2-2) described later, when a transfer method using ablation by laser is used, the substrate 91 can be any substrate that is transmissive to the laser, and quartz glass having a high light transmittance at all wavelengths is particularly preferred. In addition, for example, in the re-transfer step (B2-2) described later, when the transfer substrate 90 is bonded to the wiring substrate 20 and the light emitting element 80 is transferred, the substrate 91 may also have a silicone layer, for example.
[0120] In the transfer step (B2-1), similarly to the above-described first embodiment, for example, a transfer method using ablation with laser light, called laser lift-off, can be used.
[0121] Fig.15 2 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred onto a light-emitting element arranged on a transfer substrate by irradiating laser light from the substrate side. Fig.15 As shown, in the transfer step (B2-1), laser light is irradiated from the base material 61 side to transfer the single piece 64 of the anisotropic conductive film onto the light emitting element 80 arranged on the transfer substrate 90.
[0122] As in the first embodiment described above, the laser lift-off device described above can be used in the transfer of the anisotropic conductive film single pieces 64. By using the laser lift-off device, a shock wave is generated on the single pieces 64 irradiated with laser light at the interface between the substrate 61 and the single pieces 64 of the anisotropic conductive film, and a plurality of single pieces 64 are peeled off from the substrate 61 and lifted toward the light emitting elements 80 arranged on the transfer substrate, so that the single pieces 64 can be landed on the light emitting elements 80 with high precision.
[0123] [Re-transfer process (B2-2)] Fig.16 FIG. 1 is a cross-sectional view schematically showing a state in which the light-emitting element transferred to the single chip is transferred to the wiring substrate. Fig.16 As shown, in the re-transfer process (B2-2), the light emitting element 80 to which the single chip 64 is transferred is re-transferred onto the wiring substrate 70. The re-transfer method is not particularly limited, but examples thereof include a method in which the light emitting element 80 to which the single chip 64 is transferred is directly transferred from a transfer substrate 90 by a laser lift-off method (LLO method) and arranged on the wiring substrate 70, and a method in which the light emitting element 80 is transferred from a transfer substrate 90 to which the light emitting element 80 to which the single chip 64 is transferred is closely attached in advance and arranged on the wiring substrate 70.
[0124] In the re-transfer process (B2-2), the light emitting element 80 is preferably transferred in units of sub-pixels constituting one pixel. This allows the light emitting element array to be adapted from a high PPI (Pixels Per Inch) light emitting element array to a low PPI light emitting element array.
[0125] [Installation process (C2)] In the mounting step (C2), the light emitting elements 80 arranged at predetermined positions on the wiring substrate 70 are mounted via the chip 64. The light emitting elements 80 are mounted in a state similar to that of the substrate 70. Fig.11 The method of connecting the light emitting element 80 to the wiring substrate 70 is the same as that of the first embodiment. Thus, in a state where there is no anisotropic conductive film between the light emitting elements 80 and the wiring substrate 70 is exposed, the light emitting element 80 can be anisotropically connected to the wiring substrate 70. In addition, by setting the wiring substrate 70 as a light-transmitting substrate, it is possible to obtain excellent light transmittance compared to the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate 70.
[0126] [Variation of the Second Embodiment] In the transfer step (B2-1) in the second embodiment described above, Fig.14 and Fig.15As shown in FIG. 1 , the single piece 64 of the anisotropic conductive film is transferred onto the light emitting element 80, but the present invention is not limited thereto. For example, the single piece of the anisotropic conductive film may be transferred onto the light emitting element in units of electrodes. Fig.13 As in the modified example of the first embodiment shown, the first and second single pieces may be transferred and mounted on, for example, the first conductive electrode 82 on the p-side and the second conductive electrode 83 on the n-side of the light emitting element 80. This can further improve the transparency of the display device.
[0127] As described above, according to the manufacturing method of the display device involved in the second embodiment, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the light emitting element 80 with high accuracy and high efficiency by irradiation with laser, so that the takt time can be shortened. In addition, excellent light transmittance, conductivity and insulation can be obtained, which cannot be achieved in the connection of providing the conventional ACP, ACF, NCF, adhesive, etc. on the entire surface, and a high-brightness and high-definition transparent display can be obtained.
[0128] [Repair process] In the display device involved in the above-mentioned embodiment, for example, when there is an unlit light-emitting element, after removing the unlit light-emitting element using the above-mentioned laser lift-off device, the single piece of the curable resin film can be transferred to the corresponding part again to repair the installation of the light-emitting element. In the laser lift-off device, the display device having a wiring substrate on which light-emitting elements are arranged is held on a donor stage, and laser light is irradiated from the wiring substrate side to peel off the desired light-emitting element and single piece, and the light-emitting element and single piece peeled from the wiring substrate are received by the acceptor substrate. In this embodiment, the wiring substrate is exposed between the single pieces, so it is preferable to perform the repair in units of single pieces.
[0129] Furthermore, in the above-mentioned embodiments, a method for manufacturing a display device as a display is cited as an example, but the present technology is not limited thereto, and for example, it can also be applied to a method for manufacturing a light-emitting device as a light source.
[0130] <4. Display device> The display device according to the present embodiment can be obtained by the manufacturing method of the display device described above. That is, the display device includes a plurality of light-emitting elements, a wiring substrate for arranging the light-emitting elements, and a cured film connecting the plurality of light-emitting elements to the wiring substrate, wherein the cured film is a single piece of a predetermined shape formed by curing a curable resin film.
[0131] The shape of the individual pieces is preferably at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle. Thus, the substrate can be exposed between the individual pieces, and excellent light transmittance or appearance can be obtained.
[0132] As mentioned above Fig.11 and Fig.13 As shown, the display device includes a plurality of light emitting elements 80 , a substrate 70 on which the light emitting elements 80 are arranged, and a cured film connecting the plurality of light emitting elements 80 and the substrate 70 .
[0133] The cured film is a film formed by curing a single piece of a curable resin film of a predetermined shape. The arrangement of the single pieces on the substrate 70 is not particularly limited as long as the light transmittance effect can be obtained, but it is preferably a sub-pixel unit corresponding to the light-emitting element 80. By arranging the single pieces in sub-pixel units, the exposed portion of the substrate between the single pieces can be increased, and very excellent light transmittance can be obtained. In addition, a single piece can also be used to connect multiple light-emitting elements 80 close to each other in a sub-pixel unit. In this way, the installation speed can be shortened (the installation efficiency can be accelerated), and the range of allowable specifications can be expanded according to the transparency or color conditions on the substrate side.
[0134] In addition, the single piece composed of the cured film is preferably a cured film of an adhesive film, a conductive film containing conductive particles, or an anisotropic conductive film. Thus, even if the light-emitting element 80 is not provided with a connection portion such as a solder bump, a plurality of light-emitting elements 80 can be connected to the substrate 70. In addition, when the electrodes of the light-emitting element 80 are in a protruding shape and an electrical connection with the wiring of the substrate 70 can be obtained, it does not matter if the single piece does not contain conductive particles.
[0135] The cured film of the anisotropic conductive film is preferably formed by arranging the conductive particles in the surface direction. By arranging the conductive particles in the surface direction, the particle surface density becomes uniform, and the conductivity and insulation can be improved. The so-called state of the conductive particles arranged in the surface direction, for example, can be listed with a plane lattice pattern having more than one arrangement axis of the conductive particles arranged in a predetermined direction at a predetermined interval, and can list rhombic lattices, hexagonal lattices, square lattices, rectangular lattices, parallelograms, etc. In addition, the arrangement of the surface direction of the conductive particles can be either random or have a plurality of regions with different plane lattice patterns.
[0136] The particle surface density of the cured film of the anisotropic conductive film can be appropriately designed according to the electrode size of the light emitting element 80, and the lower limit of the particle surface density can be set to 500 particles / mm. 2 Above, 20000 pieces / mm 2 Above, 40000 pieces / mm 2 Above, 50000 pieces / mm 2 The upper limit of the particle surface density can be set to 1500000 particles / mm 2 Below, 1,000,000 pieces / mm 2 Below, 500,000 pieces / mm 2 Below, 100,000 pieces / mm2 As a result, even when the electrode size of the light emitting element 80 is small, excellent conductivity and insulation can be obtained.
[0137] The particle surface density of the cured film of anisotropic conductive film is the particle surface density of the conductive particles during film formation during manufacture. This is the same whether the particle surface density of the randomly configured part is measured or the particle surface density of the arranged part is measured. In the case of obtaining the particle number density based on a plurality of monoliths, the particle surface density can be obtained based on the area and the number of particles after removing the interval between the monoliths from the area containing the monoliths and the intervals. Regarding the monoliths, sometimes it is inappropriate to express it with the number density, and sometimes it is appropriate to express it with the occupied area ratio of the particles in one monolith or the particle diameter and the center distance between the particles and the number.
[0138] In addition, the particle surface density of the cured film of the anisotropic conductive film is the particle surface density of the conductive particles during film formation during manufacture. This is the same whether it is measuring the particle surface density of the randomly configured part or measuring the particle surface density of the arranged part. In the case of obtaining the particle number density according to a plurality of monoliths, the particle surface density can be obtained according to the area and the number of particles after removing the interval between the monoliths from the area containing the monoliths and the intervals. Regarding the monoliths, it is inappropriate to represent the situation with the number density sometimes, and it is appropriate to represent the situation with the occupied area ratio of the particles in one monolith or the particle diameter and the center distance between the particles and the number sometimes.
[0139] The number of conductive particles in each single piece can be appropriately designed according to the electrode size of the light-emitting element 80. The lower limit is, for example, more than 2, preferably more than 4, and more preferably more than 10, and the upper limit is less than 6000, preferably less than 500, and more preferably less than 100.
[0140] The average transmittance of visible light after the monolithic sheet is placed (set) on the substrate is preferably 20% or more, more preferably 35% or more, and further preferably 50% or more. Thus, a display device with excellent light transmittance or beauty can be obtained. Even in the case of a substrate that is not opaque, the monolithic sheet can be pasted on plain glass or a transparent substrate for evaluation, and the average transmittance can be calculated using it as a reference (Ref). The average transmittance of visible light with a light-emitting element is lower. When a light-emitting element is installed, it is set to be measured in an unlit state. For example, an ultraviolet-visible spectrophotometer can be used to measure the average transmittance of visible light.
[0141] The size of the monolithic chip relative to the size of the light emitting element may be smaller than the size of the light emitting element 80 as long as conductivity is obtained. In addition, as long as the light transmittance effect of the display device is obtained, the monolithic chip may be arranged in such a manner that it exists not only directly under the light emitting element but also in the peripheral portion.
[0142] The amount of protrusion of the single chip from the light emitting element 80 is preferably less than 30 μm, more preferably less than 10 μm, and further preferably less than 5 μm. In addition, when the single chip does not protrude, the protrusion may be zero or a negative number. Thus, compared with the configuration example of a display device in which a cured film is provided on the entire surface of the substrate, a superior light transmittance can be obtained. In addition, the amount of protrusion of the single chip from the light emitting element 80 is the maximum value of the distance from the periphery of the light emitting element 80 to the periphery of the single chip.
[0143] According to the display device involved in this embodiment, by having an exposed portion for exposing the substrate 70 between the single pieces of the cured film, it is possible to obtain excellent light transmittance, conductivity and insulation that cannot be achieved in the connection of the previous ACP, ACF, NCF, adhesive, etc. provided on the entire surface, and a high-brightness and high-definition transparent display can be obtained.
[0144] In addition, in the above-mentioned embodiment, a display device as a display in which the light-emitting elements 80 are arranged in units of sub-pixels is cited as an example, but the present technology is not limited to this, and can also be applied to a light-emitting device as a light source. The light-emitting device includes a plurality of light-emitting elements, a substrate for arranging the light-emitting elements, and a cured film connecting the plurality of light-emitting elements to the substrate, and the cured film is composed of a plurality of single pieces, and has an exposed portion between the single pieces for exposing the substrate. According to such a light-emitting device, the light-emitting element 80 is made into a micro size, and the number of chips obtained per wafer is increased, so that the price can be reduced, and the industrial advantage of thinning or energy saving of the light-emitting device can be obtained.
[0145] In addition, in the above, a formation process is described as a part of a suitable embodiment of the present technology, in which a laser is irradiated from the substrate side to a curable resin film provided on the aforementioned substrate, the curable resin film in the irradiated portion is removed, and a single piece of a predetermined shape composed of a curable resin film having a reaction rate of less than 25% is formed on the aforementioned substrate.
[0146] Here, removing the curable resin film by laser irradiation does not only mean completely peeling off or removing the curable resin film, but also includes partially peeling off or removing the curable resin film.
[0147] Furthermore, the curable resin film may not necessarily be removed, but may be modified (for example, cured, softened, etc.) by laser irradiation so as to facilitate efficient transfer in the subsequent transfer process of the individual sheets. Of course, removal and modification may be combined.
[0148] In addition, the single piece of a predetermined shape formed on the substrate does not necessarily need to be a curable resin film with a reaction rate of 25% or less, as long as it is a desired resin film. As the desired resin film, for example, a curable resin film with a reaction rate exceeding 25% or a non-curable resin film such as a thermoplastic resin film can be cited. In addition, it can also be a cured film obtained by curing the resin film. Example
[0149] <5. Example> In this example, the anisotropic conductive film was processed into a single piece, and the shape state of the single piece was evaluated. In addition, the single piece was transferred to a glass plate, and the transfer state of the single piece was evaluated. In addition, the present technology is not limited to these examples.
[0150] The anisotropic conductive film substrate was prepared, the single-piece processing was evaluated, and the single-piece transfer was evaluated as follows.
[0151] [Fabrication of anisotropic conductive film substrate] 42 parts by mass of a phenoxy resin (trade name: PKHH, manufactured by Basashi Chemical Industry Co., Ltd.), 40 parts by mass of a high-purity bisphenol A epoxy resin (trade name: YL-980, manufactured by Mitsubishi Chemical Corporation), 10 parts by mass of a hydrophobic silica (trade name: R202, manufactured by Nippon Aerosil Co., Ltd.), 3 parts by mass of an acrylic rubber (trade name: SG80H, manufactured by Nagase ChemteX Co., Ltd.) and 5 parts by mass of a cationic polymerization initiator (trade name: SI-60L, manufactured by Sanshin Chemical Industry Co., Ltd.) were mixed, applied on a 4-inch quartz glass and dried to prepare a resin film.
[0152] Conductive particles (average particle size 2.2 μm, resin core metal coated particles, 0.2 μm thick Ni plating, manufactured by Sekisui Chemical Co., Ltd.) were press-transferred to the obtained resin film by the method described in Japanese Patent No. 6187665, so that one interface of the resin film was roughly aligned with the conductive particles, and a 4.0 μm thick particle surface density of 580,000 particles / mm was provided on a 4-inch quartz glass. 2 An anisotropic conductive film substrate of an anisotropic conductive film. The arrangement of conductive particles in the anisotropic conductive film in a plan view is a hexagonal lattice arrangement.
[0153] [Evaluation of single chip processing] (Normal ratio of shape) After the anisotropic conductive film is processed into individual sheets, 1000 sheets are randomly selected from the individual sheets (a total of 10000 sheets), and the number of sheets with normal shape (no curling or defect) is counted by visual inspection under a microscope (for curling or defect, refer to the above Figure 4 (B) shows a curled piece 42 or a chipped piece 43.) Then, the shape normality rate is calculated using the following formula. The normality rate is preferably 95% or more. Normal rate = number of normal-shaped pieces / total number × 100
[0154] (Burr generation rate) After the anisotropic conductive film was processed into individual sheets, the number of burrs generated was counted for all the individual sheets (a total of 10,000 pieces), and the shape normality was calculated using the following formula (for burrs, refer to Figure 4 (A) shows a single piece 41 with burrs. The number of burrs generated is preferably 10% or less. Burr generation rate = number of burrs / total number of single pieces × 100
[0155] (Response rate) The reaction rate of the single piece was measured using FT-IR (Varian 3100FT-IR (Excalibur series) microscope Varian 600UMA (FT-IR microscope)). First, after laser irradiation, a sharp-tipped pen-shaped cutter was used to sample the single piece remaining on the substrate to obtain a sample after laser irradiation. Next, a set of two diamond units was used to clamp the sampled single piece sample between two unit plates and tighten and flatten them, and one unit plate with the single piece sample was used for measurement.
[0156] The detector is cooled in advance to greatly improve its sensitivity, so the detector is cooled in advance with liquid nitrogen for about 30 minutes before measurement. In addition, the measurement conditions of FT-IR are set as follows. Measuring method: Transmission Measurement temperature: 25℃ Measuring humidity: below 60% Measuring time: 12 seconds Detector spectral range: 4000 to 700 cm -1
[0157] Furthermore, the diamond unit was placed at an infrared microscope, and background measurement was performed to irradiate the sample after laser irradiation with infrared rays. After laser irradiation, the IR spectrum of the single piece remaining on the substrate was obtained. In addition, as with the sample after laser irradiation, a pen-shaped cutter with a sharp tip was used to sample the curable resin film before laser irradiation (before singulation), and the IR spectrum of the curable resin film before laser irradiation was obtained. Regarding the reaction rate, the methyl group (2930cm -1 Nearby) and epoxy (914cm -1 The peak height of the epoxy group (around 1000 nm) is calculated as the ratio of the peak height of the epoxy group to the peak height of the methyl group before and after the reaction (before and after laser irradiation) as shown in the following formula. The reaction rate is preferably 25% or less. Reaction rate (%) = {1-(a / b) / (A / B)}×100 In the above formula, A is the peak height of the epoxy group before the reaction, B is the peak height of the methyl group before the reaction, a is the peak height of the epoxy group after the reaction, and b is the peak height of the methyl group after the reaction.
[0158] [Evaluation of single-sheet transfer] 1000 pieces of anisotropic conductive film were transferred to a glass substrate using a laser lift-off device (LUM-XTR manufactured by Shin-Etsu Engineering). Figure 1 As shown, the laser lift-off device includes, for example, a laser scanner for scanning the optical axis of the laser, a mask having a plurality of openings of a predetermined shape arranged at a predetermined pitch, a projection lens for reducing and projecting the laser onto a donor substrate, a donor stage for holding the donor substrate, and an acceptor stage for holding an acceptor substrate. A quartz glass substrate formed with a single piece is held on the donor stage, and a glass substrate is held on the acceptor stage, and the distance between the single piece and the glass substrate is set to 100 μm.
[0159] The laser device used was an excimer laser with an oscillation wavelength of 248 nm. The laser pulse energy was 600 J and the energy density (fluence) was 180 J / cm 2 , the pulse width (irradiation time) is 30000 picoseconds, the pulse frequency is 0.01 kHz, and the number of irradiation pulses is set to 1 pulse for each single chip.
[0160] The pulse energy of the laser beam irradiated to the interface between the single piece of anisotropic conductive film and the quartz glass for imaging is 0.001 to 2 J, and the energy density (fluence) is 0.001 to 2 J / cm 2 , the pulse width (irradiation time) is 0.01 to 1×10 9 Picoseconds, pulse frequency is 0.1 to 10000 Hz, and the number of irradiation pulses is set from 1 to 30000000.
[0161] The mask uses a pattern in which windows of a predetermined pitch and size are arranged so that the projection of the single piece of anisotropic conductive film as the donor substrate at the interface with the quartz glass has a size of the single piece (30 μm in horizontal direction × 40 μm in vertical direction or 60 μm in horizontal direction × 80 μm in vertical direction) at a pitch of 120 μm in horizontal direction and 160 μm in vertical direction. Furthermore, the optical axis of the laser is scanned toward the opening on the mask along the X-axis direction and the Y-axis direction, and the pulse irradiation of the laser is controlled to transfer the single piece to the glass substrate of the receptor stage.
[0162] (yield rate) 1000 sheets transferred onto the glass substrate were observed under a microscope, and the sheets with good transfer shapes and good transfer were counted, and the yield rate of the sheets was calculated using the following formula. The yield rate was preferably 85% or more. In addition, good transfer shape means that there is no curling or defect (for curling or defect, refer to the above Figure 4 (B) shows a curled sheet 42 or a defective sheet 43). Good transfer means that the transfer is to a designated location (see the following). Fig.17 The position of the single piece before and after transfer is shown). Number of good products = number of good transfer products / total number × 100
[0163] (Transfer position accuracy) 1000 pieces were transferred from quartz glass to quartz glass repeatedly 25 times using a laser lift-off device (LUM-XTR manufactured by Shin-Etsu Engineering), and the positional deviation after transfer was evaluated based on the position of the piece before transfer.
[0164] Fig.17 This is a diagram for explaining the positional deviation of a single sheet before and after transfer. The straight-line distance d from the reference position P0 (X0, Y0) before transfer to the position P1 (X1, Y1) after transfer of each single sheet is calculated by the following formula (1), and the average value is obtained. Regarding the evaluation of the transfer position accuracy, the following judgments A to E are set according to the average value of the straight-line movement distance. It is expected that the evaluation of the transfer position accuracy is C or above.
[0165] [Number 1] A: Less than 5μm B: 5μm or more and less than 10μm C: 10 μm or more and less than 15 μm D: 15μm or more and less than 20μm E: 20μm or more
[0166] [Evaluation of lighting test] In this example, a lighting evaluation was performed on a mounted body in which a μLED element was mounted using the processed single chip. The mounted body was produced and the lighting evaluation was performed as follows.
[0167] (Manufacturing of mounting body) Fig.18 is a diagram schematically showing a method for manufacturing a mounting body, Fig.18 (A) shows the process of preparing a single piece, Fig.18 (B) shows the process of transferring the single piece to the substrate, Fig.18 (C) shows the process of temporarily fixing the μLED element. Fig.18 (D) shows the step of press-bonding the μLED element. Fig.19 is a top view schematically showing an evaluation substrate used for a lighting test, Fig. 20 (A) is a top view schematically showing the electrode surface of a μLED element, Fig. 20 (B) is a diagram schematically showing a state where a μLED element is mounted on an evaluation substrate.
[0168] like Fig.18 As shown in (A), first, a single piece 104 of a predetermined shape processed on the aforementioned quartz glass 101 is prepared. Fig.18 As shown in (B), laser light is irradiated from the back side (quartz glass 101 side) of the single piece 104 to transfer the single piece 104 to a predetermined position of the evaluation substrate 107. The transfer of the single piece 104 is performed in the same manner as in the LLO in the evaluation of the single piece transfer described above.
[0169] The evaluation substrate 107 has a wiring pattern formed on a glass substrate with a thickness of 0.5 mm, with a base of Cr having a thickness of 20 nm and a surface of Au having a thickness of 80 nm. Fig.19 As shown in FIG. 1 , an evaluation substrate having 15 sets of 6-tooth first comb-shaped electrodes 107A and 6-tooth second comb-shaped electrodes 107B was used. Fig.19 and Fig. 20 As shown in (B), the wiring pattern uses a comb-tooth line width of 90μm, a spacing width of 12μm or 24μm, and a wiring pattern of approximately 1300μm×15ch≈19.3mm per channel, and a single piece of a predetermined shape is transferred between wirings with a spacing width of 12μm.
[0170] Then, if Fig.18 As shown in (C), the polydimethylsiloxane (PDMS) sheet 109 with the μLED elements 108 arranged side by side on the convex part is aligned by LLO in advance and bonded under the conditions of 30°C-30MPa-10 seconds. Fig. 20 As shown in (B), the μLED element 108 is temporarily fixed between wirings with a spacing width of 12 μm on the evaluation substrate 107 via the single piece 104 .
[0171] like Fig. 20 As shown in (A), the μLED element 108 has an outer diameter of 34 μm×58 μm, a size of the first electrode 108A and the second electrode 108B of 27 μm×18 μm, and a distance of 16 μm between the first electrode 108A and the second electrode 108B.
[0172] Then, if Fig.18 As shown in (D), the μLED elements 108 are pressed together by applying pressure under the pressing conditions of 150° C., 150 N, and 30 seconds, thereby manufacturing a mounted body having μLED elements (3600 in total).
[0173] (Light up the review) A voltage of 3.0 V was applied to the first and second comb-shaped electrodes of the mounting body, the number of lit μLED elements (3600 in total) was counted, and the lighting rate was calculated using the following formula: The lighting rate was preferably 95% or more. Lighting rate = lighting number / total number × 100
[0174] <Example 1> [Single-sheet processing of anisotropic conductive films] Using a laser lift-off device (LUM-XTR manufactured by Shin-Etsu Engineering), laser is irradiated from the quartz glass side of the aforementioned anisotropic conductive film substrate to transfer the unnecessary portion to the plain glass, thereby forming a single piece of anisotropic conductive film on the quartz glass. Figure 1 As shown, the laser stripping device, for example, has a laser scanner for scanning the optical axis of the laser, a mask having a plurality of openings of a predetermined shape arranged at a predetermined interval, a projection lens for reducing and projecting the laser onto a donor substrate, a donor stage for holding the donor substrate, and an acceptor stage for holding an acceptor substrate. An anisotropic conductive film substrate serving as the donor substrate is held on the donor stage, and plain glass serving as the acceptor substrate is held on the acceptor stage, and the distance between the anisotropic conductive film and the plain glass is set to 100 μm.
[0175] The laser device used was an excimer laser with an oscillation wavelength of 248 nm. The laser pulse energy was 600 J and the energy density (fluence) was 250 J / cm 2 , the pulse width (irradiation time) is 30000 picoseconds, the pulse frequency is 0.01 kHz, and the number of irradiation pulses is set to 1 pulse for each single chip.
[0176] The pulse energy of the imaging laser irradiated to the interface between the anisotropic conductive film and the quartz glass is 0.001 to 2 J, and the energy density (fluence) is 0.001 to 2 J / cm 2 , the pulse width (irradiation time) is 0.01 to 1×109 Picoseconds, pulse frequency is 0.1 to 10000 Hz, and the number of irradiation pulses is set from 1 to 30000000.
[0177] Fig.21 Schematically shows the top view of the mask shape of Example 1. Fig.21 As shown, in Example 1, a mask having a 125 μm×125 μm quadrilateral window is used to set the laser spot to a quadrilateral shape. After removing the unnecessary portion of the anisotropic conductive film in the longitudinal direction at the quadrilateral pitch of the mask window, the unnecessary portion of the anisotropic conductive film in the transverse direction is removed at the quadrilateral pitch of the mask window, and 100×100 (a total of 10,000) single pieces of 30 μm horizontal×40 μm vertical quadrilaterals are formed at a 120 μm horizontal pitch and a 160 μm vertical pitch.
[0178] As shown in Table 1, the normal rate of the single-chip processing in Example 1 is 100%, the burr generation rate of the single-chip processing is 2%, and the reaction rate of the single-chip processing is less than 20%. In addition, the yield rate of the single-chip transfer in Example 1 is 96%, and the evaluation of the position accuracy is C. In addition, the μLED elements of the good parts of the single-chip transfer are lit, so the lighting rate of the lighting test in Example 1 is the same as the yield rate of the single-chip transfer.
[0179] <Example 2> As in Example 1, 100×100 pieces (10,000 pieces in total) of single pieces of 60 μm in width×80 μm in length were formed with a pitch of 120 μm in width and a pitch of 160 μm in length.
[0180] As shown in Table 1, the normal rate of single-chip processing in Example 2 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 2 is more than 99%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 2 is the same as the yield rate of single-chip transfer.
[0181] <Example 3> Fig. 22 Schematically shows the top view of the mask shape of Example 3. Fig. 22 As shown, in Example 3, a mask having a 70 μm×70 μm quadrilateral window portion is used to set the laser spot to a quadrilateral shape. In addition, as in Example 1, 100×100 (a total of 10,000) quadrilateral single pieces of 30 μm horizontally and 40 μm vertically are formed with a 120 μm horizontal pitch and a 160 μm vertical pitch.
[0182] As shown in Table 1, the normal rate of single-chip processing in Example 3 is 100%, the burr generation rate of single-chip processing is 5%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 3 is 93%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 3 is the same as the yield rate of single-chip transfer.
[0183] <Example 4> Fig.23 Schematically shows the top view of the mask shape of Example 4. Fig.23 As shown, in Example 4, a mask having a 30 μm horizontal × 40 μm vertical light shielding portion in the center of a 125 μm × 125 μm quadrilateral window is used to set the laser spot to a shape having a quadrilateral shadow in the center of the quadrilateral. In addition, in addition to removing unnecessary portions of the anisotropic conductive film at the quadrilateral pitch in the longitudinal direction or the lateral direction of the window of the mask, 100 × 100 (a total of 10,000) quadrilateral single pieces of 30 μm horizontal × 40 μm vertical are formed at a 120 μm horizontal pitch and a 160 μm vertical pitch as in Example 1.
[0184] As shown in Table 1, the normal rate of single-chip processing in Example 4 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 4 is more than 99%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 4 is the same as the yield rate of single-chip transfer.
[0185] <Example 5> Fig.24 Schematically shows the top view of the mask shape of Example 5. Fig.24 As shown, in Example 5, a mask having a 60 μm horizontal × 80 μm vertical light shielding portion in the center of a 158 μm × 158 μm quadrilateral window is used to set the laser spot to a shape having a quadrilateral shadow in the center of the quadrilateral. In addition, in addition to removing unnecessary portions of the anisotropic conductive film at the quadrilateral pitch in the longitudinal direction or the lateral direction of the window of the mask, 100 × 100 (a total of 10,000) quadrilateral single pieces of 60 μm horizontal × 80 μm vertical are formed at a pitch of 120 μm horizontally and 160 μm vertically as in Example 1.
[0186] Fig.25 : is a microscope photograph showing a single piece of a quadrilateral of Example 5. Fig.25 As shown, the single chip of Example 5 and Fig.24 The size of the quadrilaterals of the light shielding parts of the mask shown is roughly the same. In addition, regarding the single piece of the quadrilateral, the unnecessary part is torn off by LLO, so the appearance is not a beautiful straight line, but a jagged shape.
[0187] As shown in Table 1, the normal rate of single-chip processing in Example 5 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 5 is more than 99%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 5 is the same as the yield rate of single-chip transfer.
[0188] <Example 6> Fig.26 Schematically shows the top view of the mask shape of Example 6. Fig.26 As shown, in Example 6, a mask having a light shielding portion of 30 μm in width and 40 μm in length at the center of a 80 μm×80 μm quadrilateral window is used to set the laser spot to a shape having a quadrilateral shadow at the center of the quadrilateral. In addition, in addition to removing unnecessary portions of the anisotropic conductive film at the quadrilateral pitch in the longitudinal direction or the lateral direction of the window of the mask, 100×100 (a total of 10,000) quadrilateral sheets of 30 μm in width and 40 μm in length are formed at a pitch of 120 μm in width and 160 μm in length as in Example 1.
[0189] As shown in Table 1, the normal rate of single-chip processing in Example 6 is 100%, the burr generation rate of single-chip processing is 1%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 6 is 97%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 6 is the same as the yield rate of single-chip transfer.
[0190] <Example 7> Fig. 27 is a top view schematically showing the mask shape of Example 7. Fig. 27 As shown, in Example 7, a mask having a square-shaped light shielding portion with rounded corners of 30 μm in width and 40 μm in length in the center of a square window of 125 μm×125 μm is used to set the laser spot to a shape of a shadow with rounded corners of a square in the center of the square. In addition, in addition to removing unnecessary parts of the anisotropic conductive film at the square pitch in the longitudinal direction or the lateral direction of the window of the mask, 100×100 (a total of 10,000) square-shaped rounded corners of 30 μm in width and 40 μm in length are formed at a 120 μm pitch in width and a 160 μm pitch in length as in Example 1.
[0191] As shown in Table 2, the normal rate of single-chip processing in Example 7 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 7 is more than 99%, and the evaluation of position accuracy is C. In addition, the lighting rate of the lighting test in Example 7 is the same as the yield rate of single-chip transfer.
[0192] <Example 8> Fig.28 Schematically shows the top view of the mask shape of Example 8. Fig.28 As shown, in Example 8, a mask having an elliptical light shielding portion of 60 μm in width and 80 μm in length at the center of a 158 μm×158 μm quadrilateral window is used to set the laser spot to a shape having an elliptical shadow at the center of the quadrilateral. In addition, in addition to removing unnecessary portions of the anisotropic conductive film at the pitch of the quadrilateral in the longitudinal direction or the lateral direction of the window of the mask, 100×100 (a total of 10,000) elliptical sheets of 60 μm in width and 80 μm in length are formed at a pitch of 120 μm in width and 160 μm in length as in Example 1.
[0193] Fig.29 : is a microscope photograph showing a single piece of the ellipse of Example 8. Fig.29 As shown, the single chip of Example 8 and Fig.28 The elliptical sizes of the light shielding parts of the masks shown are roughly the same. In addition, the elliptical single piece has a more beautiful appearance than the quadrilateral single piece. This is believed to be because: compared with the quadrilateral single piece, there are fewer parts designed in a straight line.
[0194] As shown in Table 2, the normal rate of single-chip processing in Example 8 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 8 is more than 99%, and the evaluation of position accuracy is B. In addition, the lighting rate of the lighting test in Example 8 is the same as the yield rate of single-chip transfer.
[0195] <Example 9> Fig.30 Schematically shows the top view of the mask shape of Example 9. Fig.30As shown, in Example 9, a mask having a circular light shielding portion of 80 μm in width and 80 μm in length at the center of a 158 μm×158 μm quadrilateral window is used to set the laser spot to a shape having a circular shadow at the center of the quadrilateral. In addition, in addition to removing unnecessary parts of the anisotropic conductive film at the pitch of the quadrilateral in the longitudinal direction or the lateral direction of the window of the mask, 100×100 (a total of 10,000) circular single pieces of 80 μm in width and 80 μm in length are formed at a pitch of 120 μm in width and 160 μm in length as in Example 1.
[0196] Fig.31 : is a microscope photograph showing a circular single piece of Example 9. Fig.31 As shown, the single chip of Example 9 and Fig.30 The circular size of the light shielding portion of the mask shown is roughly the same. In addition, the circular single piece has a more beautiful appearance than the quadrilateral single piece. This is believed to be because: compared with the quadrilateral single piece, there are fewer parts designed in a straight line.
[0197] As shown in Table 2, the normal rate of single-chip processing in Example 9 is 100%, the burr generation rate of single-chip processing is 0%, and the reaction rate of single-chip processing is less than 20%. In addition, the yield rate of single-chip transfer in Example 9 is more than 99%, and the evaluation of position accuracy is A. In addition, the lighting rate of the lighting test in Example 9 is the same as the yield rate of single-chip transfer.
[0198] <Comparative Example 1> Using a laser lift-off device (LUM-XTR manufactured by Shin-Etsu Engineering), laser was irradiated from the side of the anisotropic conductive film bonded to a 4-inch quartz glass, and unnecessary portions were sublimated by laser ablation, thereby forming a single piece of anisotropic conductive film on the quartz glass.
[0199] The laser device used was an excimer laser with an oscillation wavelength of 248 nm. The laser pulse energy was 600 J and the energy density (fluence) was 500 J / cm 2 , the pulse width (irradiation time) is 30000 picoseconds, the pulse frequency is 0.01 kHz, and the number of irradiation pulses is set to 10 pulses for each single chip.
[0200] The mask used a mask having a 125 μm×125 μm quadrilateral window portion, and the laser spot was set to a quadrilateral shape. After removing the unnecessary portion of the anisotropic conductive film in the longitudinal direction at the quadrilateral pitch of the mask window portion in the longitudinal direction, the unnecessary portion of the anisotropic conductive film in the transverse direction was removed at the quadrilateral pitch of the mask window portion in the longitudinal direction, and 100×100 (a total of 10,000) single pieces of quadrilaterals of 30 μm in width and 40 μm in length were formed at a 120 μm horizontal pitch and a 160 μm vertical pitch.
[0201] As shown in Table 2, the normal rate of single-chip processing in Comparative Example 1 is 100%, the burr generation rate of single-chip processing is 2%, and the reaction rate of single-chip processing is more than 70%. In addition, the good rate of single-chip transfer in Comparative Example 1 is 0%, and the evaluation of position accuracy is E.
[0202] <Comparative Example 2> An attempt was made to process 100×100 (a total of 10,000) single pieces of 60 μm in width and 80 μm in length with a 120 μm horizontal pitch and a 160 μm vertical pitch using a blade dicing device with a 20 μm blade, but single piece processing was not possible. As shown in Table 2, the normal rate of single piece processing in Comparative Example 2 was 0%.
[0203] Table 1 shows the evaluation results of the single-wafer processing and the evaluation results of the single-wafer transfer of Examples 1 to 6, and Table 2 shows the evaluation results of the single-wafer processing and the evaluation results of the single-wafer transfer of Examples 7 to 9 and Comparative Examples 1 and 2.
[0204] [Table 1]
[0205] [Table 2]
[0206] The reaction rate of the single piece of Comparative Example 1 is as high as 70% or more. This is believed to be because: since the laser is irradiated from the anisotropic conductive film side, the energy density or the number of irradiation pulses used to sublimate the unnecessary part is large, and the surrounding single pieces are also affected by radiant heat. In addition, the reaction rate of the single piece of Comparative Example 1 is high, so it is difficult to transfer the single piece. Comparative Example 2 uses a blade cutting device, so it is impossible to produce a small single piece of 60μm horizontal × 80μm vertical.
[0207] Examples 1 to 9 use a laser stripping device to irradiate laser from the substrate side to remove the anisotropic conductive film of the irradiated portion, so that the reaction rate of the single chip can be set to less than 25%. Therefore, excellent evaluation results of single chip processing and evaluation results of single chip transfer can be obtained. In addition, Examples 4 to 9 can suppress the generation rate of burrs by using a mask having a shading portion in the shape of a single chip in the opening window. This is considered to be because: the anisotropic conductive film on the periphery of the single chip can be reliably removed by a mask having a shading portion in the shape of a single chip. In addition, Examples 7 to 9 can obtain particularly excellent evaluation results of single chip transfer. This is considered to be because there are no acute angles in the shape of the single chip, so that curling or defects in the transferred single chip can be suppressed. In addition, the lighting rate of the lighting test in Examples 1 to 9 is the same as the yield rate of single chip transfer. Description of Reference Numerals
[0208] 10 Laser lift-off device, 11 Laser scanner, 12 Mask, 13 Projection lens, 20 Curable resin film substrate, 21 Base material, 22 Curable resin film, 23 Removal portion, 30 Curable resin film substrate, 31 Base material, 32 Curable resin film, 33 Removal portion, 34 Single piece, 41 Single piece with burrs, 42 Single piece with curling, 43 Single piece with defects, 51 Light shielding portion, 52 Single piece, 53 Light shielding portion, 54A to 54D Light shielding portions, 60 Single piece film, 61 Base material, 62 Anisotropic conductive Film, 63 conductive particles, 64 monolithic chip, 64A monolithic chip, 64B monolithic chip, 70 wiring substrate, 71 substrate, 72 first electrode, 73 second electrode, 80 light-emitting element, 81 main body, 82 first conductive type electrode, 83 second conductive type electrode, 90 transfer substrate, 91 substrate, 101 quartz glass, 104 monolithic chip, 107 evaluation substrate, 107A first comb-type electrode, 107B second comb-type electrode, 108 μLED element, 108A first electrode, 108B second electrode, 109 PDMS sheet.
Claims
1. A mask having a light shielding portion of a predetermined shape for shielding laser light in an opening for transmitting laser light, Laser light is transmitted through the outer periphery of the light shielding portion.
2. The mask according to claim 1, wherein The predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle.
3. A method for manufacturing a mask, comprising removing a light-shielding film from a light-transmitting substrate so that a light-shielding portion having a predetermined shape for shielding laser light is provided in an opening for transmitting laser light.
4. A method for manufacturing a display device, comprising: A forming step of irradiating a curable resin film provided on the substrate with a laser from the substrate side, removing the curable resin film in the irradiated portion, and forming a single piece of a predetermined shape composed of a curable resin film having a reaction rate of 25% or less on the substrate; a transfer step of transferring the single piece of the predetermined shape to a predetermined position of a wiring substrate or an electrode surface of a light-emitting element; and A mounting step of mounting the light emitting element on the wiring substrate via the transferred single piece.
5. The method for manufacturing a display device according to claim 4, wherein: In the forming step, the laser beam is irradiated through a mask on which a light shielding portion having the predetermined shape is formed.
6. The method for manufacturing a display device according to claim 4, wherein: In the transfer step, laser light is irradiated from the substrate side to transfer the single piece of the predetermined shape to a predetermined position of a wiring board or an electrode surface of a light emitting element.
7. The method for manufacturing a display device according to claim 4, wherein: The predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle.
8. The method for manufacturing a display device according to claim 4, wherein: The single sheets are arranged on the substrate.
9. The method for manufacturing a display device according to claim 8, wherein: The distance between the individual pieces is greater than 10 μm.
10. A display device comprising: a plurality of light emitting elements; a wiring substrate on which the light emitting elements are arranged; and a cured film that connects the plurality of light emitting elements to the wiring substrate, The cured film is formed by curing a single piece of a predetermined shape composed of a curable resin film. The predetermined shape is at least one selected from a polygon formed by obtuse angles, a polygon with rounded corners, an ellipse, an oval, and a circle.
11. The display device according to claim 10, wherein: The distance between the individual pieces is greater than 10 μm.
12. The display device according to claim 10, wherein: The light emitting elements are arranged in units of sub-pixels constituting one pixel.
13. The display device according to claim 10, wherein: The single chips are arranged on the wiring substrate in units of sub-pixels or pixels.
Citation Information
Patent Citations
Di-or tetrahydroisoquinoline derivatives, manufacture and medicinal composition
JP1986087665A
MANUFACTURING METHOD OF D03-TYPE Fe3Al PARTICLE POWDER
JP2022145312A
Display device using semiconductor light emitting device
US20150255505A1